A highly conductive porous carbon material, preparation method and application thereof in energy storage devices
By using the combination technology of sulfonated polystyrene microspheres, modified carbon nanotubes and Ni/Co-MOF materials in MOF-derived porous carbon materials, poor conductivity and insufficient specific surface area are solved by combining the formation of molybdenum disulfide nanosheets. The problem has significantly improved the electrochemical properties of porous carbon materials.
Patent Information
- Application Number
- CN202411330907.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-24
- Publication Date
- 2024-12-31
- Estimated Expiration
- 2044-09-24
Smart Images

Figure CN118866563B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of porous carbon material preparation, and relates to a highly conductive porous carbon material, a preparation method and application thereof in energy storage equipment. Background Art
[0002] According to the different energy storage mechanisms, supercapacitors can be divided into two types, namely: double-layer capacitors and pseudocapacitors. Double-layer capacitors are based on the accumulation of static electricity at the interface between electrodes and electrolytes for energy storage. Commonly used electrode materials include carbon-based porous materials such as activated carbon, carbon nanotubes, and carbon aerogels. It is worth noting that the charging and discharging process of double-layer capacitors mainly occurs on the surface of the electrode material, so the electrochemical performance of the capacitor depends largely on the specific surface area of the electrode material.
[0003] Metal-Organic Frameworks (MOF) are crystalline materials with periodic network structures formed by self-assembly of metal ions and organic ligands. MOF materials have the characteristics of high specific surface area, diverse ligands and metal centers, controllable pore size and functional structure. Derivatives obtained with MOF materials as precursors have nanoporous structures with uniform pore size, high porosity and controllable morphology, such as porous carbon or metal oxide nanostructures. The porous structure is usually produced by the decomposition of organic ligands or the evaporation of MOF metals at high temperatures. Among MOF-derived materials, porous carbon has a high specific surface area and abundant active sites, and the graphitized carbon produced by high-temperature carbonization gives porous carbon conductivity, which is a very promising electrode material.
[0004] However, MOF-derived porous carbon also has obvious defects, such as poor conductivity due to low degree of graphitization and small specific surface area of some MOFs such as ZIF-67. These defects limit the further application of MOF-derived porous carbon in the field of supercapacitors. Therefore, it is urgent to improve the conductivity and specific surface area of MOF-derived porous carbon to broaden the application scenarios of MOF-derived porous carbon. Summary of the invention
[0005] In view of the deficiencies in the prior art, the object of the present invention is to provide a highly conductive porous carbon material, a preparation method and application thereof in energy storage devices.
[0006] To achieve this object, the present invention adopts the following technical solutions:
[0007] In a first aspect, the present invention provides a method for preparing a highly conductive porous carbon material, the preparation method comprising:
[0008] Firstly, polystyrene microspheres are sulfonated and coated with polydopamine to obtain coated modified polystyrene microspheres;
[0009] Subsequently, the carbon nanotubes are modified to obtain modified carbon nanotubes; cobalt and nickel are used as metal centers, 2-methylimidazole is used as an organic ligand, and the modified carbon nanotubes are used as conductive fillers. A composite porous material composed of the modified carbon nanotubes and the Ni / Co-MOF material is synthesized in situ on the surface of the coated modified polystyrene microspheres by a hydrothermal synthesis method, and finally a hollow carbon sphere precursor composed of the coated modified polystyrene microspheres and the composite porous material loaded on the surface of the coated modified polystyrene microspheres is obtained;
[0010] Finally, ammonium molybdate and thiourea are used as raw materials to generate molybdenum disulfide nanosheets by in-situ reaction on the surface of the hollow carbon sphere precursor to obtain the highly conductive porous carbon material.
[0011] As a preferred technical solution of the present invention, the preparation method specifically comprises the following steps:
[0012] (I) adding microsphere seeds, dibutyl phthalate and toluene to a sodium dodecyl sulfate solution, while mechanically stirring and heating in a water bath to obtain a microsphere emulsion; adding styrene monomer, divinylbenzene monomer and 2,2-azobisisobutyronitrile to the sodium dodecyl sulfate solution, mixing uniformly to obtain a microsphere precursor solution; adding the microsphere precursor solution to the microsphere emulsion, mixing uniformly to obtain a reaction precursor solution, adding a polyvinyl alcohol solution to the reaction precursor solution, mixing uniformly to obtain a reaction solution, heating and stirring the reaction solution in an anaerobic environment to react, and sequentially washing the reaction product with deionized water, Soxhlet extraction, anhydrous ethanol washing, centrifugal separation and vacuum drying to obtain polystyrene microspheres;
[0013] (II) dispersing the polystyrene microspheres obtained in step (I) in an ethanol aqueous solution, ultrasonically dispersing to obtain a microsphere dispersion liquid, adding concentrated sulfuric acid to the microsphere dispersion liquid, ultrasonically dispersing to obtain a sulfonated microsphere solution, heating and stirring the sulfonated microsphere solution to react, filtering, washing and drying after the reaction to obtain sulfonated polystyrene microspheres; dissolving dopamine in a Tris-HCl buffer, mixing uniformly to obtain a dopamine solution; dispersing the sulfonated polystyrene microspheres in the dopamine solution, stirring at room temperature to allow dopamine to polymerize in situ on the surface of the sulfonated polystyrene microspheres to form a polydopamine layer, and then filtering, washing and drying to obtain coated modified polystyrene microspheres;
[0014] (III) dispersing carbon nanotubes in a mixed acid solution composed of concentrated sulfuric acid and concentrated nitric acid, obtaining a first dispersion after ultrasonic dispersion, heating and stirring the first dispersion, and then filtering, washing and drying to obtain first carbon nanotubes; dispersing the first carbon nanotubes in an acidic hydrogen peroxide solution to obtain a second dispersion, applying high temperature and high pressure to the second dispersion under a protective atmosphere to react, and obtaining second carbon nanotubes after the reaction; uniformly mixing the second carbon nanotubes, polyethylene glycol 2000, polyvinyl pyrrolidone and deionized water to obtain a third dispersion, refluxing the third dispersion under a nitrogen atmosphere, and filtering, washing and drying to obtain modified carbon nanotubes after the reaction;
[0015] (IV) mixing the modified carbon nanotubes, polyvinyl pyrrolidone and methanol obtained in step (III), and obtaining a carbon nanotube suspension by ultrasonic dispersion, adding cobalt nitrate hexahydrate and nickel nitrate hexahydrate to the carbon nanotube suspension, and obtaining a metal salt solution by ultrasonic dispersion, and adding the coated modified polystyrene microspheres obtained in step (II) to the metal salt solution, and mixing them uniformly to obtain a precursor solution; dissolving 2-methylimidazole in methanol to obtain an organic ligand solution; and uniformly mixing the precursor solution and the organic ligand solution to obtain a carbon sphere precursor solution, subjecting the carbon sphere precursor solution to a hydrothermal reaction, and washing, centrifuging and drying the reaction product obtained by the reaction to obtain a hollow carbon sphere precursor;
[0016] (V) spreading the hollow carbon sphere precursor obtained in step (IV) in a first porcelain boat, spreading sodium hypophosphite in a second porcelain boat, placing the first porcelain boat and the second porcelain boat in a tubular furnace with a distance therebetween, introducing a mixed gas of hydrogen and nitrogen into the tubular furnace, performing a phosphating reaction on the hollow carbon sphere precursor, washing and drying the reaction product obtained by the reaction, and obtaining a phosphated hollow carbon sphere precursor; heating the phosphated hollow carbon sphere precursor to a first temperature at a first heating rate and keeping the temperature, then heating the phosphated hollow carbon sphere precursor to a second temperature at a second heating rate and keeping the temperature, and finally cooling the precursor to room temperature with the furnace to complete the carbonization treatment and obtain a hollow carbon sphere composite material;
[0017] (VI) dispersing the hollow carbon sphere composite material obtained in step (V) in anhydrous ethanol to obtain a carbon sphere dispersion; dissolving ammonium molybdate and thiourea in anhydrous ethanol to obtain a MoS2 precursor solution; mixing the carbon sphere dispersion with the MoS2 precursor solution, and obtaining a reaction mixture after ultrasonic dispersion; heating the reaction mixture to a third temperature at a third heating rate and keeping the temperature, and then heating the reaction mixture to a fourth temperature at a fourth heating rate and keeping the temperature, and cooling the reaction mixture to room temperature in the furnace after the insulation is completed, so that ammonium molybdate and thiourea react to generate molybdenum disulfide nanosheets and load them on the surface of the hollow carbon sphere composite material to obtain the highly conductive porous carbon material.
[0018] The preparation method provided by the present invention uses sulfonated polystyrene microspheres as template sacrificial materials, and forms a polydopamine layer on the surface of the sulfonated polystyrene microspheres through in-situ oxidation self-polymerization; subsequently, cobalt and nickel are used as metal centers, 2-methylimidazole is used as an organic ligand, and modified carbon nanotubes are used as conductive fillers. A composite porous material composed of modified carbon nanotubes and Ni / Co-MOF materials is synthesized by a hydrothermal synthesis method, and the composite porous material is loaded on the surface of the polydopamine layer. During the high-temperature carbonization process, the polydopamine layer forms a spherical structure carbon shell skeleton with micropores, and the polystyrene microspheres inside it are decomposed into carbon dioxide and water vapor at high temperature, and the composite porous material loaded on the surface of the polydopamine layer forms a multi-porous carbon structure with stacked sheets. Finally, the hollow carbon sphere composite material obtained after carbonization is mixed with a MoS2 precursor solution, and molybdenum disulfide nanosheets are synthesized in situ on the surface of the hollow carbon sphere composite material through a hydrothermal reaction, and finally a highly conductive porous carbon material with excellent electrochemical properties is prepared.
[0019] The present invention adopts monodisperse polystyrene microspheres as microsphere seeds, and prepares polystyrene microspheres with a mesoporous structure by a two-step swelling polymerization method. In the preparation process of the polystyrene microspheres, dibutyl phthalate and toluene are used as composite swelling agents. Although dibutyl phthalate is a good solvent for polystyrene microspheres, the surface of the obtained polystyrene microspheres presents sponge-like pores with a small average pore size, but the adsorption capacity of dibutyl phthalate to styrene monomers and divinylbenzene monomers is weak, resulting in a small portion of styrene monomers and divinylbenzene monomers being in a free state, so that the styrene monomers and divinylbenzene monomers undergo polymerization reaction outside the microsphere seeds, and thus the finally obtained polystyrene microspheres contain free small particle impurities. The addition of toluene improves the ability of the microsphere seeds to adsorb monomers after swelling, so that the obtained polystyrene microspheres hardly contain small particle impurities. In addition, the addition of toluene will increase the specific surface area of the polystyrene microspheres and reduce the average pore size. This is because the addition of toluene increases the adsorption capacity of the swollen microsphere seeds for the monomer, which increases the monomer concentration inside the microsphere seeds, increases the degree of phase separation during polymerization, and divides the solution phase into smaller droplets by the cross-linked structure, ultimately resulting in an increase in the proportion of small pores in the obtained polystyrene microspheres, a smaller pore size, and an increase in the number of micropores.
[0020] The present invention uses a mixed acid solution composed of concentrated sulfuric acid and concentrated nitric acid and an acidic hydrogen peroxide solution to perform oxidation modification on carbon nanotubes. The tube wall of the unmodified carbon nanotube is relatively complete, a stable six-membered ring structure is formed between carbon atoms, and only the carbon atoms at both ends of the carbon nanotube have unsaturated bonds. The unsaturated bonds have good activity. A large number of defects appear on the tube wall of the carbon nanotube after the oxidation modification treatment, and these defects increase the number of carbon atoms with unsaturated bonds. At the same time, the carbon atoms at the defects will also form active functional groups such as hydroxyl and carboxyl due to oxidation. In the process of hydrothermal synthesis of hollow carbon sphere precursors, cobalt ions and nickel ions are easily combined with these active functional groups in the modified carbon nanotubes, and finally firmly attached to the surface of the modified carbon nanotubes, so that the hollow carbon sphere precursor is bonded to the carbon atoms with unsaturated bonds. This bonding can effectively improve the electron transmission between the hollow carbon sphere precursor and the modified carbon nanotube, which is beneficial to improving the capacitance characteristics of the porous carbon material.
[0021] In the preparation process of the modified carbon nanotubes provided by the present invention, the carbon nanotubes are first subjected to an oxidation treatment by a mixed acid solution composed of concentrated sulfuric acid and concentrated nitric acid, and the functional groups other than carboxyl groups on the outer surface and inner wall of the carbon nanotubes are oxidized to carboxyl groups by utilizing the strong oxidizing property of the mixed acid solution, thereby obtaining a first carbon nanotube rich in hydroxyl groups and carboxyl groups. Subsequently, the first carbon nanotubes are subjected to a secondary oxidation treatment by an acidic hydrogen peroxide solution, which, on the one hand, can further remove the byproducts formed on the outer surface and inner wall of the first carbon nanotubes during the treatment with the mixed acid solution, thereby preventing these byproducts from adversely affecting the subsequent reaction of the carbon nanotubes with polyethylene glycol 2000; on the other hand, the carboxyl groups on the surface of the first carbon nanotubes can be removed, and only the carboxyl groups on the inner wall of the first carbon nanotubes are retained, and the second carbon nanotubes are obtained after being treated with the acidic hydrogen peroxide solution. Finally, the second carbon nanotube is mixed with polyethylene glycol 2000 and dispersant polyvinyl pyrrolidone solution and refluxed. Since there is no carboxyl group on the outer surface of the second carbon nanotube, the hydroxyl group in polyethylene glycol 2000 can only react with the carboxyl group on the inner wall of the second carbon nanotube, so that the polyethylene glycol 2000 polymer chain forms a "bridge" structure inside the carbon nanotube, which reduces the diameter of the modified carbon nanotube to a certain extent, improves the mechanical properties of the modified carbon nanotube, and is beneficial to improve the peeling phenomenon of the porous carbon material caused by volume change during the charge and discharge process; at the same time, the modified carbon nanotube with a smaller diameter forms a transmission channel for electrolyte ions, which greatly improves the conductive properties of the porous carbon material.
[0022] For MOF materials, having a binary metal active center usually means having more abundant reaction sites and higher electrochemical activity than a single metal active center. In addition, the synergistic effect between different metal sites can also improve the conductivity of MOFs materials to a certain extent and make its framework structure more stable. In view of the similar elemental properties of cobalt and nickel, and the cobalt ion also has a higher theoretical specific capacitance, the present invention chooses to introduce cobalt metal active sites on the basis of Ni-MOF materials, thereby constructing a Ni / Co-MOF binary metal organic framework to improve the electrochemical performance of the porous carbon material finally prepared.
[0023] The invention uses cobalt and nickel as metal centers, 2-methylimidazole as organic ligands, and modified carbon nanotubes as conductive fillers. A composite porous material composed of modified carbon nanotubes and Ni / Co-MOF materials is prepared by a hydrothermal synthesis method in a mixed solvent system composed of polyvinyl pyrrolidone and methanol. During the hydrothermal reaction, the composite porous material is uniformly loaded on the surface of coated modified polystyrene microspheres, and finally a hollow carbon sphere precursor is obtained. The hollow carbon sphere precursor includes polystyrene microspheres as sacrificial hard templates, a polydopamine layer coated on the surface of the polystyrene microspheres through an oxidative self-polymerization reaction, and a composite porous material composed of modified carbon nanotubes and Ni / Co-MOF materials in situ loaded on the surface of the polydopamine layer through a hydrothermal synthesis process.
[0024] The introduction of cobalt ions greatly affects the crystal growth environment of Ni-MOF materials, significantly reducing the crystallinity of Ni-MOF materials and enhancing structural disorder, which leads to the refinement of crystal particles of Ni-MOF materials, which is conducive to the transmission of electrolyte ions. At the same time, low crystalline phase materials have excellent structural stability. Therefore, Ni / Co-MOF materials have a strong ability to buffer strain during the charge and discharge process, and the rate performance of the prepared porous carbon materials will also be improved to a certain extent. In addition, since cobalt ions have a high theoretical specific capacitance, under the synergistic effect of Ni and Co binary metal centers, the capacitance value of the highly conductive porous carbon materials finally prepared can also be greatly improved.
[0025] The Ni / Co-MOF material formed by the hydrothermal synthesis reaction of the present invention presents a three-dimensional porous nanostructure dominated by mesopores, which is formed by cross-linking and stacking nanosheets, and there are a large number of pores and gaps between the nanosheet layers. The exposed active surface of the nanosheet provides considerable metal active sites for the electrochemical reaction, which can significantly improve the specific capacitance of the porous carbon material; in addition, the unique three-dimensional porous structure of the Ni / Co-MOF material is conducive to the penetration of the electrolyte, provides a convenient channel for the transmission and diffusion of electrolyte ions, and promotes the electrochemical reaction kinetics of the porous carbon material.
[0026] The charge storage of carbon nanotubes is based on the double electric layer principle. Compared with the pseudocapacitor, the contribution of the comparative capacitance is smaller. In the hydrothermal reaction process of the Ni / Co-MOF material, an appropriate amount of modified carbon nanotubes is introduced into the present invention, and the surface defects and active functional groups of the modified carbon nanotubes are used as the growth center of the Ni / Co-MOF material, so as to provide the nucleation sites of the Ni / Co-MOF material crystals and allow heterogeneous nucleation, and finally form a loose porous composite porous material in which the modified carbon nanotubes and the Ni / Co-MOF material are interwoven, overlapped and entangled with each other. The self-assembly synthesis characteristics of the Ni / Co-MOF material are utilized to realize the composite with the modified carbon nanotubes, the microscopic morphology of the Ni / Co-MOF material is optimized, the original dense sheet stacking structure of the Ni / Co-MOF material is improved, and a continuous two-dimensional loose structure is formed, which can not only provide abundant accessible space and electrochemical active sites for electrolyte ions, but also contribute to the rapid penetration of electrolyte ions and the improvement of electrochemical reaction kinetics.
[0027] The advantages of the continuous two-dimensional loose structure composed of modified carbon nanotubes and Ni / Co-MOF materials are: (1) The nanosheet structure of Ni / Co-MOF materials provides abundant active sites for the electrochemical reaction, and the formed three-dimensional multi-porous structure facilitates the rapid penetration of electrolyte ions and has a good buffering effect on the volume change during long-term cycling; the modified carbon nanotubes act as a "connecting bridge" to connect Ni / Co-MOF nanosheets, thereby continuously transferring electrons to the active center, increasing the specific surface area of the material while also enhancing the stability of its bulk structure. (2) The irregular gaps formed between the nanosheets of Ni / Co-MOF materials, between the nanosheets and the modified carbon nanotubes, and between the modified carbon nanotubes not only provide channels for the rapid transmission of electrolyte ions, but also play a disturbing role to a certain extent, which is conducive to the diffusion of electrolyte ions to the active sites and the generation of pseudocapacitance. (3) The modified carbon nanotubes have excellent electrical conductivity, which can enhance the electrical conductivity of the material, thereby promoting the transmission of electrons in the redox reaction, and to a certain extent make up for the lack of electrical conductivity of the Ni / Co-MOF material. At the same time, the active functional groups such as hydroxyl and carboxyl groups on the surface of the carbon nanotubes after oxidation modification can also improve the surface wettability of the highly conductive porous carbon material. Therefore, the synergistic effect between the Ni / Co-MOF material and the carbon nanotubes makes the final prepared porous carbon material have the excellent properties of both pseudocapacitance and double electric layer.
[0028] Molybdenum disulfide nanosheets have a layered structure similar to graphite. The sandwich layers of S-Mo-S are connected by weak van der Waals forces, and the interlayer spacing is about 0.62nm, which is much larger than the 0.34nm of graphite. The larger interlayer spacing allows it to provide more electrolyte ion storage space, so its theoretical specific capacity is higher. However, the biggest defect of molybdenum disulfide nanosheets is that its huge volume expansion can cause electrode pulverization and separation of the material from the current collector, resulting in poor cycle performance of porous carbon materials. The present invention mixes the hollow carbon ball composite material with the MoS2 precursor solution, and synthesizes molybdenum disulfide nanosheets in situ on the surface of the hollow carbon ball composite material through a hydrothermal synthesis reaction. The layered material molybdenum disulfide nanosheets are matched with the Ni / Co-MOF material, so that the surface of the carbon shell skeleton forms abundant porous channels, which greatly improves the specific surface area of the porous carbon material, is conducive to promoting the rapid diffusion of electrolyte ions, thereby allowing electrolyte ions of different sizes to contact the material surface, and at the same time provides abundant active sites for electrochemical reactions during charging and discharging.
[0029] In the present invention, a synergistic effect is produced between the molybdenum disulfide nanosheets, the Ni / Co-MOF material and the modified carbon nanotubes, which is specifically embodied in:
[0030] (1) Lamellar MoS2 has a large specific surface area and nanoscale, which can significantly reduce the diffusion time and distance of electrolyte ions during the charge and discharge process. In addition, lamellar MoS2 loaded on the surface of modified carbon nanotubes can be combined with Ni / Co-MOF materials with the same lamellar structure to form a multi-channel pore structure to store electrolyte ions, thereby improving the utilization rate of electrolyte ions.
[0031] (2) When modified carbon nanotubes are not added, electrolyte ions can only be transmitted within the two-dimensional sheet plane of the molybdenum disulfide nanosheet or the Ni / Co-MOF nanosheet. However, due to the steric hindrance between the molybdenum disulfide nanosheet and the Ni / Co-MOF nanosheet, the transmission of electrolyte ions between the molybdenum disulfide nanosheet and the Ni / Co-MOF nanosheet is relatively difficult, and a continuous and effective ion transmission path cannot be formed, resulting in a significant reduction in the transmission speed of the electrolyte ions. The present invention adds modified carbon nanotubes, which can serve as a "conductive bridge" to connect between the molybdenum disulfide nanosheet and the Ni / Co-MOF nanosheet, thereby solving the problem of poor ion transmission paths between different sheets.
[0032] (3) After high-temperature carbonization, the Ni / Co-MOF material retains a complete carbon skeleton structure, providing a solid mechanical support platform for the in-situ growth of MoS2 nanosheets on the surface. In addition, during the hydrothermal reaction, a small amount of uncarbonized Ni / Co-MOF material will dehydrate to form oligomers. At the same time, ammonium molybdate and thiourea will also generate MoS2 nanosheets. Since the interlayer force of MoS2 nanosheets is mainly van der Waals force, when the oligomer enters the interlayer of MoS2 nanosheets, the oligomer molecules will continue to Dehydration carbonization forms colloidal carbon. The entry of colloidal carbon prevents the continued stacking of MoS2 sheets, resulting in a decrease in the number of layers of the formed MoS2 nanosheets and an increase in the interlayer spacing. The reduction in the number of MoS2 nanosheets can effectively inhibit the drastic volume change of MoS2 nanosheets during the electrochemical reaction, avoid morphological deformation during the charge and discharge process, and alleviate the volume expansion of MoS2 nanosheets during the charge and discharge process. The increase in the interlayer spacing of MoS2 nanosheets allows the electrolyte ions to be quickly embedded and removed.
[0033] As a preferred technical solution of the present invention, in step (I), the particle size of the microsphere seed is 2-3 μm, for example, it can be 2.0 μm, 2.1 μm, 2.2 μm, 2.3 μm, 2.4 μm, 2.5 μm, 2.6 μm, 2.7 μm, 2.8 μm, 2.9 μm or 3.0 μm, but it is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0034] In some optional examples, the mass fraction of the sodium dodecyl sulfate solution is 0.2~0.3wt%, for example, it can be 0.2wt%, 0.21wt%, 0.22wt%, 0.23wt%, 0.24wt%, 0.25wt%, 0.26wt%, 0.27wt%, 0.28wt%, 0.29wt% or 0.3wt%, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0035] In some optional examples, the ratio of the microsphere seed, the dibutyl phthalate, the toluene and the sodium dodecyl sulfate solution is 1g: (5-10) mL: (15-20) mL: (100-150) mL, for example, it can be 1g: 5mL: 15mL: 100mL, 1g: 5.5mL: 15.5mL: 105mL, 1g: 6mL: 16mL: 110mL, 1g: 6.5mL: 16.5mL: 115mL, 1g :7mL:17mL:120mL, 1g:7.5mL:17.5mL:125mL, 1g:8mL:18mL:130mL, 1g:8.5mL:18.5mL:135mL, 1g:9mL:19mL:140mL, 1g:9.5mL:19.5mL:145mL or 1g:10mL:20mL:150mL, but is not limited to the listed values, other values not listed within the numerical range are also applicable.
[0036] In some optional examples, the rotation speed of the mechanical stirring is 400~500rpm, for example, it can be 400rpm, 410rpm, 420rpm, 430rpm, 440rpm, 450rpm, 460rpm, 470rpm, 480rpm, 490rpm or 500rpm, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0037] In some optional embodiments, the water bath heating temperature is 30-40°C, for example, it can be 30°C, 31°C, 32°C, 33°C, 34°C, 35°C, 36°C, 37°C, 38°C, 39°C or 40°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0038] In some optional embodiments, the water bath heating time is 20 to 30 hours, for example, it can be 20 hours, 21 hours, 22 hours, 23 hours, 24 hours, 25 hours, 26 hours, 27 hours, 28 hours, 29 hours or 30 hours, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0039] In some optional examples, the ratio of the total volume of the styrene monomer and the divinylbenzene monomer to the volume of the sodium dodecyl sulfate solution is (0.02~0.03):1, for example, it can be 0.02:1, 0.021:1, 0.022:1, 0.023:1, 0.024:1, 0.025:1, 0.026:1, 0.027:1, 0.028:1, 0.029:1 or 0.03:1, but is not limited to the listed values, and other unlisted values within the numerical range are equally applicable.
[0040] In some optional examples, the volume ratio of the styrene monomer to the divinylbenzene monomer is 1:(0.4~0.5), for example, it can be 1:0.4, 1:0.41, 1:0.42, 1:0.43, 1:0.44, 1:0.45, 1:0.46, 1:0.47, 1:0.48, 1:0.49 or 1:0.5, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0041] In some optional examples, the mass ratio of the 2,2-azobisisobutyronitrile to the styrene monomer is (0.02~0.03):1, for example, it can be 0.02:1, 0.021:1, 0.022:1, 0.023:1, 0.024:1, 0.025:1, 0.026:1, 0.027:1, 0.028:1, 0.029:1 or 0.03:1, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0042] In some optional examples, the mass ratio of the styrene monomer in the microsphere precursor solution to the microsphere seeds in the microsphere emulsion is (100-120):1, for example, it can be 100:1, 102:1, 104:1, 106:1, 108:1, 110:1, 112:1, 114:1, 116:1, 118:1 or 120:1, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0043] In some optional examples, the mass ratio of the styrene monomer in the reaction precursor solution to the polyvinyl alcohol in the polyvinyl alcohol solution is (0.1~0.2):1, for example, it can be 0.1:1, 0.11:1, 0.12:1, 0.13:1, 0.14:1, 0.15:1, 0.16:1, 0.17:1, 0.18:1, 0.19:1 or 0.2:1, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0044] In some optional examples, the mass fraction of the polyvinyl alcohol solution is 10~12wt%, for example, it can be 10wt%, 10.2wt%, 10.4wt%, 10.6wt%, 10.8wt%, 11wt%, 11.2wt%, 11.4wt%, 11.6wt%, 11.8wt% or 12wt%, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0045] In some optional examples, the stirring rate of the reaction solution is 100~150rpm, for example, it can be 100rpm, 105rpm, 110rpm, 115rpm, 120rpm, 125rpm, 130rpm, 135rpm, 140rpm, 145rpm or 150rpm, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0046] In some optional examples, the heating temperature of the reaction solution is 65-75°C, for example, it can be 65°C, 66°C, 67°C, 68°C, 69°C, 70°C, 71°C, 72°C, 73°C, 74°C or 75°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0047] In some optional examples, the heating time of the reaction solution is 20 to 30 hours, for example, it can be 20 hours, 21 hours, 22 hours, 23 hours, 24 hours, 25 hours, 26 hours, 27 hours, 28 hours, 29 hours or 30 hours, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0048] In some optional examples, the solvent used in the Soxhlet extraction is obtained by mixing methanol and acetic acid in a volume ratio of (8~9):(1~2), for example, it can be 8:2, 8.1:1.9, 8.2:1.8, 8.3:1.7, 8.4:1.6, 8.5:1.5, 8.6:1.4, 8.7:1.3, 8.8:1.2, 8.9:1.1 or 9:1, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0049] In some optional embodiments, the Soxhlet extraction time is 5 to 10 hours, for example, it can be 5.0 hours, 5.5 hours, 6.0 hours, 6.5 hours, 7.0 hours, 7.5 hours, 8.0 hours, 8.5 hours, 9.0 hours, 9.5 hours or 10.0 hours, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0050] In some optional embodiments, the temperature of the Soxhlet extraction is 75-85°C, for example, it can be 75°C, 76°C, 77°C, 78°C, 79°C, 80°C, 81°C, 82°C, 83°C, 84°C or 85°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0051] As a preferred technical solution of the present invention, in step (II), the mass ratio of the polystyrene microspheres to the ethanol aqueous solution is 1:(20-30), for example, it can be 1:20, 1:21, 1:22, 1:23, 1:24, 1:25, 1:26, 1:27, 1:28, 1:29 or 1:30, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0052] In some optional examples, the volume ratio of ethanol to deionized water in the ethanol aqueous solution is 1:(1.5~2), for example, it can be 1:1.5, 1:1.55, 1:1.6, 1:1.65, 1:1.7, 1:1.75, 1:1.8, 1:1.85, 1:1.9, 1:1.95 or 1:2, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0053] In some optional examples, the ultrasonic power of the ultrasonic dispersion after the polystyrene microspheres are dispersed in the ethanol aqueous solution is 300-400 W, for example, it can be 300 W, 310 W, 320 W, 330 W, 340 W, 350 W, 360 W, 370 W, 380 W, 390 W or 400 W, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0054] In some optional examples, the ultrasonic dispersion time of the polystyrene microspheres after being dispersed in the ethanol aqueous solution is 1 to 2 hours, for example, it can be 1.0h, 1.1h, 1.2h, 1.3h, 1.4h, 1.5h, 1.6h, 1.7h, 1.8h, 1.9h or 2.0h, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0055] In some optional examples, the mass ratio of the polystyrene microspheres in the microsphere dispersion to the concentrated sulfuric acid is 1:(20-25), for example, 1:20, 1:20.5, 1:21, 1:21.5, 1:22, 1:22.5, 1:23, 1:23.5, 1:24, 1:24.5 or 1:25, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0056] In some optional examples, the mass fraction of the concentrated sulfuric acid is 80-90wt%, for example, it can be 80wt%, 81wt%, 82wt%, 83wt%, 84wt%, 85wt%, 86wt%, 87wt%, 88wt%, 89wt% or 90wt%, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0057] In some optional examples, the ultrasonic power of ultrasonic dispersion after adding concentrated sulfuric acid to the microsphere dispersion is 400-500 W, for example, 400 W, 410 W, 420 W, 430 W, 440 W, 450 W, 460 W, 470 W, 480 W, 490 W or 500 W, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0058] In some optional examples, the ultrasonic dispersion time after adding concentrated sulfuric acid to the microsphere dispersion is 10 to 20 minutes, for example, it can be 10 minutes, 11 minutes, 12 minutes, 13 minutes, 14 minutes, 15 minutes, 16 minutes, 17 minutes, 18 minutes, 19 minutes or 20 minutes, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0059] In some optional embodiments, the heating temperature of the sulfonated microsphere solution is 30-40°C, for example, it can be 30°C, 31°C, 32°C, 33°C, 34°C, 35°C, 36°C, 37°C, 38°C, 39°C or 40°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0060] In some optional embodiments, the heating time of the sulfonated microsphere solution is 2 to 3 hours, for example, it can be 2.0 hours, 2.1 hours, 2.2 hours, 2.3 hours, 2.4 hours, 2.5 hours, 2.6 hours, 2.7 hours, 2.8 hours, 2.9 hours or 3.0 hours, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0061] In some optional examples, the concentration of dopamine in the dopamine solution is 5-8 g / L, for example, it can be 5.0 g / L, 5.2 g / L, 5.4 g / L, 5.6 g / L, 5.8 g / L, 6.0 g / L, 6.2 g / L, 6.4 g / L, 6.6 g / L, 6.8 g / L, 7.0 g / L, 7.2 g / L, 7.4 g / L, 7.6 g / L, 7.8 g / L or 8.0 g / L, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0062] In some optional embodiments, the pH value of the dopamine solution is 8-9, for example, it can be 8.0, 8.1, 8.2, 8.3, 8.4, 8.5, 8.6, 8.7, 8.8, 8.9 or 9.0, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0063] In some optional examples, the mass ratio of the sulfonated polystyrene microspheres to dopamine in the dopamine solution is (1.5~2.5):1, for example, it can be 1.5:1, 1.6:1, 1.7:1, 1.8:1, 1.9:1, 2.0:1, 2.1:1, 2.2:1, 2.3:1, 2.4:1 or 2.5:1, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0064] The present invention particularly limits the mass ratio of sulfonated polystyrene microspheres to dopamine in the dopamine solution to (1.5-2.5):1. When the amount of dopamine added is lower than the lower limit of the range defined in the present invention, too little dopamine is deposited on the surface of the sulfonated polystyrene microspheres, the thickness of the formed polydopamine layer is thin, and the structure is unstable. In the subsequent carbonization process, the polydopamine layer is easy to collapse and a carbon shell skeleton with a complete shape cannot be formed. At the same time, a too thin carbon shell skeleton is not conducive to the attachment of Ni / Co-MOF materials and molybdenum disulfide nanosheets, and will also affect the formation of a porous structure to a certain extent.
[0065] As the amount of dopamine added increases, the amount of dopamine deposited on the surface of the sulfonated polystyrene microspheres increases, which is conducive to the formation of a polydopamine layer with a stable structure and moderate thickness, so that the carbon shell skeleton structure can still be completely preserved after the sulfonated polystyrene microspheres are removed later, without causing the carbon shell skeleton to collapse.
[0066] When the amount of dopamine added exceeds the upper limit of the range specified in the present invention, on the one hand, it will cause the polydopamine coating layer to be too thick, and the thickness of the carbon shell skeleton formed after high-temperature carbonization will be too large. The gas generated by the pyrolysis of the sulfonated polystyrene microspheres will find it difficult to break through the carbon shell skeleton and escape, resulting in a significant reduction in the number of micropores formed on the carbon shell skeleton; on the other hand, the excess dopamine cannot be completely wrapped on the surface of the sulfonated polystyrene microspheres, and the dopamine that is not coated on the surface of the sulfonated polystyrene microspheres undergoes oxidative self-polymerization, forming free irregular carbon materials after carbonization. This part of the irregular carbon material will be attached to the surface of the carbon shell skeleton in the form of physical deposition, and fill the gaps between the Ni / Co-MOF material and the molybdenum disulfide nanosheets, so that the surface area of the porous carbon material is greatly reduced, which significantly affects the electrochemical properties of the porous carbon material.
[0067] In some optional examples, the sulfonated polystyrene microspheres are dispersed in the dopamine solution and stirred for 20 to 30 hours, for example, 20 hours, 21 hours, 22 hours, 23 hours, 24 hours, 25 hours, 26 hours, 27 hours, 28 hours, 29 hours or 30 hours, but are not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0068] As a preferred technical solution of the present invention, in step (III), the molar concentration of concentrated sulfuric acid is 17-18 mol / L, for example, it can be 17 mol / L, 17.1 mol / L, 17.2 mol / L, 17.3 mol / L, 17.4 mol / L, 17.5 mol / L, 17.6 mol / L, 17.7 mol / L, 17.8 mol / L, 17.9 mol / L or 18 mol / L, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0069] In some optional examples, the molar concentration of the concentrated nitric acid is 15-16 mol / L, for example, it can be 15 mol / L, 15.1 mol / L, 15.2 mol / L, 15.3 mol / L, 15.4 mol / L, 15.5 mol / L, 15.6 mol / L, 15.7 mol / L, 15.8 mol / L, 15.9 mol / L or 16 mol / L, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0070] In some optional examples, the volume ratio of the concentrated sulfuric acid to the concentrated nitric acid is 1:(3~4), for example, it can be 1:3.0, 1:3.1, 1:3.2, 1:3.3, 1:3.4, 1:3.5, 1:3.6, 1:3.7, 1:3.8, 1:3.9 or 1:4.0, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0071] In some optional examples, the ratio of the carbon nanotubes to the mixed acid solution is 1g:(100~200)mL, for example, it can be 1g:100mL, 1g:110mL, 1g:120mL, 1g:130mL, 1g:140mL, 1g:150mL, 1g:160mL, 1g:170mL, 1g:180mL, 1g:190mL or 1g:200mL, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0072] In some optional examples, the heating temperature of the first dispersion is 50-60°C, for example, it can be 50°C, 51°C, 52°C, 53°C, 54°C, 55°C, 56°C, 57°C, 58°C, 59°C or 60°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0073] In some optional examples, the stirring time of the first dispersion is 1 to 2 hours, for example, it can be 1.0 h, 1.1 h, 1.2 h, 1.3 h, 1.4 h, 1.5 h, 1.6 h, 1.7 h, 1.8 h, 1.9 h or 2.0 h, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0074] In some optional examples, the acidic hydrogen peroxide solution is obtained by mixing glacial acetic acid, hydrogen peroxide solution and concentrated sulfuric acid in a volume ratio of (8-9):(4-5):1, for example, 8:4:1, 8.1:4.1:1, 8.2:4.2:1, 8.3:4.3:1, 8.4:4.4:1, 8.5:4.5:1, 8.6:4.6:1, 8.7:4.7:1, 8.8:4.8:1, 8.9:4.9:1 or 9:5:1; wherein the mass fraction of the hydrogen peroxide solution is 3 0~40wt%, for example, it can be 30wt%, 31wt%, 32wt%, 33wt%, 34wt%, 35wt%, 36wt%, 37wt%, 38wt%, 39wt% or 40wt%; the mass fraction of the concentrated sulfuric acid is 95~98wt%, for example, it can be 95wt%, 95.5wt%, 96wt%, 96.5wt%, 97wt%, 97.5wt% or 98wt%, but it is not limited to the listed values, and other unlisted values within the numerical range are equally applicable.
[0075] In some optional examples, the ratio of the first carbon nanotubes to the acidic hydrogen peroxide solution is 1g:(200~300)mL, for example, it can be 1g:200mL, 1g:210mL, 1g:220mL, 1g:230mL, 1g:240mL, 1g:250mL, 1g:260mL, 1g:270mL, 1g:280mL, 1g:290mL or 1g:300mL, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0076] In some optional examples, the reaction temperature of the second dispersion is 140-150°C, for example, it can be 140°C, 141°C, 142°C, 143°C, 144°C, 145°C, 146°C, 147°C, 148°C, 149°C or 150°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0077] In some optional examples, the reaction pressure of the second dispersion is 0.8~1.2MPa, for example, it can be 0.8MPa, 0.85MPa, 0.9MPa, 0.95MPa, 1.0MPa, 1.05MPa, 1.1MPa, 1.15MPa or 1.2MPa, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0078] In some optional examples, the reaction time of the second dispersion is 30 to 40 min, for example, 30 min, 31 min, 32 min, 33 min, 34 min, 35 min, 36 min, 37 min, 38 min, 39 min or 40 min, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0079] In some optional examples, the mass ratio of the polyethylene glycol 2000 to the polyvinyl pyrrolidone is (2~3):1, for example, it can be 2.0:1, 2.1:1, 2.2:1, 2.3:1, 2.4:1, 2.5:1, 2.6:1, 2.7:1, 2.8:1, 2.9:1 or 3.0:1, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0080] In some optional instances, the ratio of the total mass of the polyethylene glycol 2000 and the polyvinyl pyrrolidone to the mass of the second carbon nanotubes is (1~2):1, for example, it can be 1.0:1, 1.1:1, 1.2:1, 1.3:1, 1.4:1, 1.5:1, 1.6:1, 1.7:1, 1.8:1, 1.9:1 or 2.0:1, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0081] In some optional examples, the mass fraction of the second carbon nanotubes in the third dispersion is 1~5wt%, for example, it can be 1.0wt%, 1.5wt%, 2.0wt%, 2.5wt%, 3.0wt%, 3.5wt%, 4.0wt%, 4.5wt% or 5.0wt%, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0082] In some optional examples, before the reflux reaction begins, an acid solution is added dropwise to the third dispersion to adjust the pH value of the third dispersion to 2-4, for example, 2.0, 2.2, 2.4, 2.6, 2.8, 3.0, 3.2, 3.4, 3.6, 3.8 or 4.0, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0083] In some optional embodiments, the temperature of the reflux reaction is 80-90°C, for example, it can be 80°C, 81°C, 82°C, 83°C, 84°C, 85°C, 86°C, 87°C, 88°C, 89°C or 90°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0084] In some optional embodiments, the reflux reaction time is 3 to 5 hours, for example, it can be 3.0 hours, 3.2 hours, 3.4 hours, 3.6 hours, 3.8 hours, 4.0 hours, 4.2 hours, 4.4 hours, 4.6 hours, 4.8 hours or 5.0 hours, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0085] As a preferred technical solution of the present invention, in step (IV), the mass fraction of the modified carbon nanotubes in the carbon nanotube suspension is 20-30wt%, for example, it can be 20wt%, 21wt%, 22wt%, 23wt%, 24wt%, 25wt%, 26wt%, 27wt%, 28wt%, 29wt% or 30wt%, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0086] In some optional examples, the ratio of the modified carbon nanotubes, polyvinyl pyrrolidone and methanol is (40~50)g:(80~90)g:(90~100)L, for example, it can be 40g:80g:90L, 41g:81g:91L, 42g:82g:92L, 43g:83g:93L, 44g:84g:94L, 45g:85g:95L, 46g:86g:96L, 47g:87g:97L, 48g:88g:98L, 49g:89g:99L or 50g:90g:100L, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0087] In some optional examples, the ultrasonic power of the ultrasonic dispersion of the modified carbon nanotubes, polyvinyl pyrrolidone and methanol after mixing is 150~250W, for example, it can be 150W, 160W, 170W, 180W, 190W, 200W, 210W, 220W, 230W, 240W or 250W, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0088] In some optional examples, the ultrasonic dispersion time of the modified carbon nanotubes, polyvinyl pyrrolidone and methanol after mixing is 50 to 60 minutes, for example, it can be 50 minutes, 51 minutes, 52 minutes, 53 minutes, 54 minutes, 55 minutes, 56 minutes, 57 minutes, 58 minutes, 59 minutes or 60 minutes, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0089] In some optional examples, the mass ratio of the modified carbon nanotubes, the cobalt nitrate hexahydrate and the nickel nitrate hexahydrate in the carbon nanotube suspension is 1:(20~30):(40~50), for example, it can be 1:20:40, 1:21:41, 1:22:42, 1:23:43, 1:24:44, 1:25:45, 1:26:46, 1:27:47, 1:28:48, 1:29:49 or 1:30:50, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0090] The introduction of modified carbon nanotubes effectively improves the pore structure on the surface of porous carbon materials, making their pore size distribution more conducive to the diffusion and transmission of electrolyte ions, and its effective specific surface area is increased, which can provide abundant active sites for the reaction, which helps to improve the rate performance and cycle stability of porous carbon materials. Secondly, the introduction of modified carbon nanotubes enhances the stability of the bulk structure of the material, and to a certain extent alleviates the volume strain of porous carbon materials during the charge and discharge process. In addition, modified carbon nanotubes also have excellent conductivity, which can enhance the conductivity of porous carbon materials and promote the transmission of electrons during redox reactions.
[0091] The present invention particularly limits the mass ratio of modified carbon nanotubes, cobalt nitrate hexahydrate and nickel nitrate hexahydrate to 1:(20-30):(40-50). As the amount of modified carbon nanotubes added increases, the composite porous material composed of modified carbon nanotubes and Ni / Co-MOF material loaded on the surface of the prepared hollow carbon sphere precursor agglomerates, and the Ni / Co-MOF material wrinkles, which is not conducive to the transfer and storage of charged ions.
[0092] In some optional examples, the ultrasonic power of the ultrasonic dispersion after adding the cobalt nitrate hexahydrate and the nickel nitrate hexahydrate to the carbon nanotube suspension is 300~400W, for example, it can be 300W, 310W, 320W, 330W, 340W, 350W, 360W, 370W, 380W, 390W or 400W, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0093] In some optional examples, the ultrasonic dispersion time after adding the cobalt nitrate hexahydrate and the nickel nitrate hexahydrate to the carbon nanotube suspension is 20 to 30 minutes, for example, it can be 20 minutes, 21 minutes, 22 minutes, 23 minutes, 24 minutes, 25 minutes, 26 minutes, 27 minutes, 28 minutes, 29 minutes or 30 minutes, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0094] In some optional examples, the ratio of the total mass of cobalt nitrate hexahydrate and nickel nitrate hexahydrate in the metal salt solution to the mass of the coated modified polystyrene microspheres is (2-3):1, for example, it can be 2.0:1, 2.1:1, 2.2:1, 2.3:1, 2.4:1, 2.5:1, 2.6:1, 2.7:1, 2.8:1, 2.9:1 or 3.0:1, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0095] In some optional examples, the mass ratio of 2-methylimidazole to methanol is 1:(20~30), for example, it can be 1:20, 1:21, 1:22, 1:23, 1:24, 1:25, 1:26, 1:27, 1:28, 1:29 or 1:30, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0096] In some optional examples, the ratio of the total mass of cobalt nitrate hexahydrate and nickel nitrate hexahydrate in the precursor solution to the mass of 2-methylimidazole in the organic ligand solution is 1:(1.5~2), for example, it can be 1:1.5, 1:1.55, 1:1.6, 1:1.65, 1:1.7, 1:1.75, 1:1.8, 1:1.85, 1:1.9, 1:1.95 or 1:2, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0097] In some optional examples, the temperature of the hydrothermal reaction of the carbon sphere precursor solution is 160-170°C, for example, it can be 160°C, 161°C, 162°C, 163°C, 164°C, 165°C, 166°C, 167°C, 168°C, 169°C or 170°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0098] The present invention specifically limits the temperature of the hydrothermal reaction of the carbon sphere precursor solution to 160-170°C. When the hydrothermal reaction temperature exceeds 170°C, the prepared Ni / Co-MOF material nanosheets begin to break and fragment, and the generated fragments agglomerate, which will lead to a reduction in the contact area between the electrolyte ions and the active substance, and will also block the transmission channel of the electrolyte ions, which is not conducive to improving the electrochemical performance of the porous carbon material.
[0099] In some optional examples, the hydrothermal reaction time of the carbon sphere precursor solution is 12 to 24 hours, for example, it can be 12 hours, 13 hours, 14 hours, 15 hours, 16 hours, 17 hours, 18 hours, 19 hours, 20 hours, 21 hours, 22 hours, 23 hours or 24 hours, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0100] In some optional examples, the centrifugal separation speed is 5000~6000r / min, for example, it can be 5000r / min, 5100r / min, 5200r / min, 5300r / min, 5400r / min, 5500r / min, 5600r / min, 5700r / min, 5800r / min, 5900r / min or 6000r / min, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0101] In some optional instances, the centrifugal separation time is 3 to 5 min, for example, it can be 3.0 min, 3.2 min, 3.4 min, 3.6 min, 3.8 min, 4.0 min, 4.2 min, 4.4 min, 4.6 min, 4.8 min or 5.0 min, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0102] As a preferred technical solution of the present invention, in step (V), the mass ratio of the hollow carbon sphere precursor to the sodium hypophosphite is 1:(20~30), for example, it can be 1:20, 1:21, 1:22, 1:23, 1:24, 1:25, 1:26, 1:27, 1:28, 1:29 or 1:30, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0103] In some optional instances, the distance between the first porcelain boat and the second porcelain boat is 10~20cm, for example, it can be 10cm, 11cm, 12cm, 13cm, 14cm, 15cm, 16cm, 17cm, 18cm, 19cm or 20cm, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0104] In some optional examples, the volume ratio of hydrogen and nitrogen in the mixed gas is (1~2):(8~9), for example, it can be 1:9, 1.1:8.9, 1.2:8.8, 1.3:8.7, 1.4:8.6, 1.5:8.5, 1.6:8.4, 1.7:8.3, 1.8:8.2, 1.9:8.1 or 2:8, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0105] In some optional examples, the flow rate of the mixed gas is 90~100mL / min, for example, it can be 90mL / min, 91mL / min, 92mL / min, 93mL / min, 94mL / min, 95mL / min, 96mL / min, 97mL / min, 98mL / min, 99mL / min or 100mL / min, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0106] In some optional examples, the pressure in the tube furnace is 2~3MPa, for example, it can be 2.0MPa, 2.1MPa, 2.2MPa, 2.3MPa, 2.4MPa, 2.5MPa, 2.6MPa, 2.7MPa, 2.8MPa, 2.9MPa or 3.0MPa, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0107] In some optional examples, the heating rate of the phosphating reaction is 4-5°C / min, for example, it can be 4.0°C / min, 4.1°C / min, 4.2°C / min, 4.3°C / min, 4.4°C / min, 4.5°C / min, 4.6°C / min, 4.7°C / min, 4.8°C / min, 4.9°C / min or 5.0°C / min, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0108] In some optional embodiments, the heating temperature of the phosphating reaction is 300-400°C, for example, it can be 300°C, 310°C, 320°C, 330°C, 340°C, 350°C, 360°C, 370°C, 380°C, 390°C or 400°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0109] In some optional examples, the holding time of the phosphating reaction is 70 to 80 min, for example, it can be 70 min, 71 min, 72 min, 73 min, 74 min, 75 min, 76 min, 77 min, 78 min, 79 min or 80 min, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0110] In some optional instances, the first heating rate is 3-4°C / min, for example, 3.0°C / min, 3.1°C / min, 3.2°C / min, 3.3°C / min, 3.4°C / min, 3.5°C / min, 3.6°C / min, 3.7°C / min, 3.8°C / min, 3.9°C / min or 4.0°C / min, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0111] In some optional instances, the first temperature is 400-500°C, for example, 400°C, 410°C, 420°C, 430°C, 440°C, 450°C, 460°C, 470°C, 480°C, 490°C or 500°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0112] In some optional examples, the first temperature is kept warm for 1 to 2 hours, for example, 1.0 h, 1.1 h, 1.2 h, 1.3 h, 1.4 h, 1.5 h, 1.6 h, 1.7 h, 1.8 h, 1.9 h or 2.0 h, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0113] In some optional instances, the second heating rate is 5-6°C / min, for example, it can be 5.0°C / min, 5.1°C / min, 5.2°C / min, 5.3°C / min, 5.4°C / min, 5.5°C / min, 5.6°C / min, 5.7°C / min, 5.8°C / min, 5.9°C / min or 6.0°C / min, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0114] In some optional instances, the second temperature is 700-800°C, for example, 700°C, 710°C, 720°C, 730°C, 740°C, 750°C, 760°C, 770°C, 780°C, 790°C or 800°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0115] In some optional embodiments, the second temperature is kept warm for 2 to 3 hours, for example, 2.0 hours, 2.1 hours, 2.2 hours, 2.3 hours, 2.4 hours, 2.5 hours, 2.6 hours, 2.7 hours, 2.8 hours, 2.9 hours or 3.0 hours, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0116] As a preferred technical solution of the present invention, in step (VI), the ratio of the hollow carbon ball composite material to anhydrous ethanol is 1g:(100~200)mL, for example, it can be 1g:100mL, 1g:110mL, 1g:120mL, 1g:130mL, 1g:140mL, 1g:150mL, 1g:160mL, 1g:170mL, 1g:180mL, 1g:190mL or 1g:200mL, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0117] In some optional examples, the ratio of the ammonium molybdate, the thiourea and the anhydrous ethanol is 1g:(2~3)g:(80~90)mL, for example, it can be 1g:2g:80mL, 1g:2.1g:81mL, 1g:2.2g:82mL, 1g:2.3g:83mL, 1g:2.4g:84mL, 1g:2.5g:85mL, 1g:2.6g:86mL, 1g:2.7g:87mL, 1g:2.8g:88mL, 1g:2.9g:89mL or 1g:3g:90mL, but it is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0118] In some optional examples, the mass ratio of the hollow carbon sphere composite material in the carbon sphere dispersion to the ammonium molybdate in the MoS2 precursor solution is 1:(1.5~2.5), for example, it can be 1:1.5, 1:1.6, 1:1.7, 1:1.8, 1:1.9, 1:2.0, 1:2.1, 1:2.2, 1:2.3, 1:2.4 or 1:2.5, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0119] The present invention particularly limits the mass ratio of the hollow carbon ball composite material in the carbon ball dispersion to the ammonium molybdate in the MoS2 precursor solution to 1:(1.5~2.5). When the concentration of ammonium molybdate in the reaction system is lower than the lower limit of the range defined by the present invention, the molybdenum disulfide product finally obtained is a small-sized solid nanosphere, and a sheet structure is not formed on the surface of the solid nanosphere. This is because the concentration of ammonium molybdate in the reaction system is too low, and a nanosphere core is generated in the initial stage of the reaction, but the amount of ammonium molybdate is insufficient, and a petal-shaped cluster morphology cannot continue to grow on the surface of the nanosphere core. Therefore, the molybdenum disulfide finally obtained is a small-sized solid nanosphere, and the shape is also irregular. When the concentration of ammonium molybdate in the reaction system exceeds the upper limit of the range defined by the present invention, the molybdenum disulfide product finally obtained is a large-sized block structure. This is because the concentration of ammonium molybdate in the reaction system is too high, resulting in insufficient growth space for the molybdenum disulfide nanosheets and mutual adhesion, and finally forming block particles with irregular morphology.
[0120] In some optional examples, the ultrasonic power of the ultrasonic dispersion after the carbon sphere dispersion and the MoS2 precursor solution are mixed is 200~300W, for example, it can be 200W, 210W, 220W, 230W, 240W, 250W, 260W, 270W, 280W, 290W or 300W, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0121] In some optional examples, the ultrasonic dispersion time of the carbon sphere dispersion after mixing with the MoS2 precursor solution is 30 to 40 minutes, for example, it can be 30 minutes, 31 minutes, 32 minutes, 33 minutes, 34 minutes, 35 minutes, 36 minutes, 37 minutes, 38 minutes, 39 minutes or 40 minutes, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0122] In some optional instances, the third heating rate is 2~3℃ / min, for example, it can be 2.0℃ / min, 2.1℃ / min, 2.2℃ / min, 2.3℃ / min, 2.4℃ / min, 2.5℃ / min, 2.6℃ / min, 2.7℃ / min, 2.8℃ / min, 2.9℃ / min or 3.0℃ / min, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0123] In some optional instances, the third temperature is 100-120°C, for example, it may be 100°C, 102°C, 104°C, 106°C, 108°C, 110°C, 112°C, 114°C, 116°C, 118°C or 120°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0124] In some optional examples, the third temperature is kept warm for 4 to 5 hours, for example, 4.0 hours, 4.1 hours, 4.2 hours, 4.3 hours, 4.4 hours, 4.5 hours, 4.6 hours, 4.7 hours, 4.8 hours, 4.9 hours or 5.0 hours, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0125] In some optional instances, the fourth heating rate is 1~2℃ / min, for example, it can be 1.0℃ / min, 1.1℃ / min, 1.2℃ / min, 1.3℃ / min, 1.4℃ / min, 1.5℃ / min, 1.6℃ / min, 1.7℃ / min, 1.8℃ / min, 1.9℃ / min or 2.0℃ / min, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0126] In some optional instances, the fourth temperature is 180~200℃, for example, it can be 180℃, 182℃, 184℃, 186℃, 188℃, 190℃, 192℃, 194℃, 196℃, 198℃ or 200℃, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0127] The reaction temperature provides power for the growth of MoS2 crystals and is a key factor affecting the reaction and crystal growth rate. In order to obtain molybdenum disulfide nanosheets with ideal morphology, the present invention specifically limits the fourth temperature to 180~200°C. When the fourth temperature is lower than 180°C, the molybdenum disulfide product finally obtained is a spherical particle with uneven size distribution and irregular shape. This is because the reaction temperature is too low, resulting in a slow reaction rate, which is not conducive to the growth of the crystal nucleus in the direction of the (002) crystal plane, and therefore a lamellar structure cannot be formed. When the fourth temperature is within the range of 180~200°C, the molybdenum disulfide product obtained is a cluster of spheres with a petal-like lamellar structure, and the size of the cluster spheres is uniform and the shape is regular, which shows that this temperature range is conducive to the selective growth of the molybdenum disulfide crystal surface. When the fourth temperature continues to rise to above 200°C, the diameter of the MoS2 cluster spheres decreases, and the number of nanosheets decreases and becomes sparsely distributed. This is because the high hydrothermal temperature leads to a high-pressure environment in the hydrothermal reactor, which rapidly generates a large number of crystal nuclei in a short period of time, resulting in a decrease in grain size. At the same time, since there are no more reactants in the system to promote the continued growth of MoS2, the petal-shaped lamellar structure becomes sparse.
[0128] In some optional examples, the fourth temperature is kept warm for 6 to 8 hours, for example, 6.0 hours, 6.2 hours, 6.4 hours, 6.6 hours, 6.8 hours, 7.0 hours, 7.2 hours, 7.4 hours, 7.6 hours, 7.8 hours or 8.0 hours, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0129] In a second aspect, the present invention provides a highly conductive porous carbon material prepared by the preparation method described in the first aspect.
[0130] In a third aspect, the present invention provides a use of the highly conductive porous carbon material described in the second aspect in an energy storage device, wherein the energy storage device includes a supercapacitor.
[0131] Compared with the prior art, the present invention has the following beneficial effects:
[0132] The preparation method provided by the present invention uses sulfonated polystyrene microspheres as template sacrificial materials, and forms a polydopamine layer on the surface of the sulfonated polystyrene microspheres through in-situ oxidation self-polymerization; subsequently, cobalt and nickel are used as metal centers, 2-methylimidazole is used as an organic ligand, and modified carbon nanotubes are used as conductive fillers. A composite porous material composed of modified carbon nanotubes and Ni / Co-MOF materials is synthesized by a hydrothermal synthesis method, and the composite porous material is loaded on the surface of the polydopamine layer. During the high-temperature carbonization process, the polydopamine layer forms a spherical structure carbon shell skeleton with micropores, and the polystyrene microspheres inside it are decomposed into carbon dioxide and water vapor at high temperature, and the composite porous material loaded on the surface of the polydopamine layer forms a multi-porous carbon structure with stacked sheets. Finally, the hollow carbon sphere composite material obtained after carbonization is mixed with a MoS2 precursor solution, and molybdenum disulfide nanosheets are synthesized in situ on the surface of the hollow carbon sphere composite material through a hydrothermal reaction, and finally a highly conductive porous carbon material with excellent electrochemical properties is prepared. BRIEF DESCRIPTION OF THE DRAWINGS
[0133] Figure 1 A flow chart of the preparation process of the highly conductive porous carbon material provided in Examples 1-5 of the present invention;
[0134] Figure 2 This is a scanning electron microscope image of the polystyrene microspheres prepared in Example 1 of the present invention;
[0135] Figure 3 The infrared spectra of the polystyrene microspheres and sulfonated polystyrene microspheres prepared in Example 1 of the present invention;
[0136] Figure 4 is a scanning electron microscope image of untreated carbon nanotubes;
[0137] Figure 5 This is a scanning electron microscope image of the modified carbon nanotubes prepared in Example 1 of the present invention;
[0138] Figure 6 This is a scanning electron microscope image of the composite porous material composed of modified carbon nanotubes and Ni / Co-MOF material prepared in Example 1 of the present invention;
[0139] Figure 7 This is a transmission electron micrograph of a composite porous material composed of modified carbon nanotubes and Ni / Co-MOF material prepared in Example 1 of the present invention;
[0140] Figure 8 This is a scanning electron microscope image of the molybdenum disulfide nanosheets prepared in Example 1 of the present invention. DETAILED DESCRIPTION
[0141] The technical solution of the present invention is described in detail below in conjunction with specific embodiments and their accompanying drawings. The embodiments recorded herein are specific embodiments of the present invention, which are used to illustrate the concept of the present invention; these descriptions are explanatory and exemplary and should not be construed as limitations on the embodiments of the present invention and the scope of protection of the present invention. In addition to the embodiments recorded herein, those skilled in the art can also adopt other obvious technical solutions based on the contents disclosed in the claims of this application and its specification, including technical solutions that adopt any obvious replacements and modifications to the embodiments recorded herein.
[0142] The chemical reagents used in the embodiments and comparative examples provided by the present invention are all commercially available products, and their specifications, brands, manufacturers and other information are as follows:
[0143] Polystyrene microsphere seeds: 230081PS, purchased from Shanghai Lingjun Biotechnology Co., Ltd.;
[0144] Dibutyl phthalate: B60515-2ml, purchased from Shanghai Yuanye Biotechnology Co., Ltd.;
[0145] Toluene: purity ≥99%, purchased from Nanjing Chemical Reagent Co., Ltd.;
[0146] Sodium dodecyl sulfate: S15012-100g, purchased from Shanghai Yuanye Biotechnology Co., Ltd.;
[0147] Styrene monomer: HG022, purchased from Shandong Mantanghong New Materials Co., Ltd.;
[0148] Divinylbenzene monomer: purity ≥99%, purchased from Hubei Hengjingrui Chemical Co., Ltd.;
[0149] 2,2-Azobisisobutyronitrile: purity ≥99%, purchased from Shandong Jinyueyuan New Materials Co., Ltd.;
[0150] Polyvinyl alcohol: S30196-500g, purchased from Shanghai Yuanye Biotechnology Co., Ltd.;
[0151] Methanol: purity ≥99%, purchased from Fuchen (Tianjin) Chemical Reagent Co., Ltd.;
[0152] Acetic acid: purity ≥99%, purchased from Wuhan Jixinyibang Biotechnology Co., Ltd.;
[0153] Ethanol: purity ≥99%, purchased from Nanjing Chemical Reagent Co., Ltd.;
[0154] Concentrated sulfuric acid: C0680154025, purchased from Nanjing Chemical Reagent Co., Ltd.;
[0155] Dopamine: purity ≥99%, purchased from Hubei Shishun Biotechnology Co., Ltd.;
[0156] Tris-HCl buffer: FT-LG1039, purchased from Shanghai Fantai Biotechnology Co., Ltd.;
[0157] Carbon nanotubes: T19281-1g, purchased from Shanghai Yuanye Biotechnology Co., Ltd.;
[0158] Concentrated nitric acid: C0680130011, purchased from Nanjing Chemical Reagent Co., Ltd.;
[0159] Hydrogen peroxide: C0404510123, purchased from Nanjing Chemical Reagent Co., Ltd.;
[0160] Polyethylene glycol 2000: purity ≥99%, purchased from Nanjing Chemical Reagent Co., Ltd.;
[0161] Polyvinyl pyrrolidone: S30268-100g, purchased from Shanghai Yuanye Biotechnology Co., Ltd.;
[0162] Cobalt nitrate hexahydrate: purity ≥99%, purchased from Nanjing Chemical Reagent Co., Ltd.;
[0163] Nickel nitrate hexahydrate: purity ≥99%, purchased from Nanjing Chemical Reagent Co., Ltd.;
[0164] 2-Methylimidazole: S25048-100g, purchased from Shanghai Yuanye Biotechnology Co., Ltd.;
[0165] Sodium hypophosphite: purity ≥99%, purchased from Hubei Shixing Chemical Co., Ltd.;
[0166] Ammonium molybdate: S60776-5g, purchased from Shanghai Yuanye Biotechnology Co., Ltd.;
[0167] Thiourea: purity ≥99%, purchased from Wuhan Xinzhongke Chemical Technology Co., Ltd.
[0168] Example 1
[0169] This embodiment provides a method for preparing a highly conductive porous carbon material. Figure 1 As shown, the preparation method specifically comprises the following steps:
[0170] (1) Add polystyrene microsphere seeds with a particle size of 2 μm, dibutyl phthalate and toluene to a sodium dodecyl sulfate solution with a mass fraction of 0.2 wt%, wherein the ratio of polystyrene microsphere seeds, dibutyl phthalate, toluene and sodium dodecyl sulfate solution is 1 g:5 mL:15 mL:100 mL, and react for 20 h under mechanical stirring conditions at 400 rpm and heating in a water bath at 40°C to obtain a microsphere emulsion;
[0171] Add styrene monomer, divinylbenzene monomer and 2,2-azobisisobutyronitrile to a sodium dodecyl sulfate solution with a mass fraction of 0.2wt%, wherein the ratio of the total volume of the styrene monomer and the divinylbenzene monomer to the volume of the sodium dodecyl sulfate solution is 0.02:1, the volume ratio of the styrene monomer to the divinylbenzene monomer is 1:0.4, and the mass ratio of 2,2-azobisisobutyronitrile to the styrene monomer is 0.02:1, and mix well to obtain a microsphere precursor solution;
[0172] Adding a microsphere precursor solution to a microsphere emulsion, wherein the mass ratio of the styrene monomer in the microsphere precursor solution to the polystyrene microsphere seeds in the microsphere emulsion is 100:1, and mixing them uniformly to obtain a reaction precursor solution; adding a polyvinyl alcohol solution with a mass fraction of 10wt% to the reaction precursor solution, wherein the mass ratio of the styrene monomer in the reaction precursor solution to the polyvinyl alcohol in the polyvinyl alcohol solution is 0.1:1, and mixing them uniformly to obtain a reaction solution;
[0173] The reaction solution was heated to 65°C in an anaerobic environment and stirred at 150 rpm for 30 hours. The reaction product was washed with deionized water, extracted with Soxhlet, washed with anhydrous ethanol, centrifuged and vacuum dried in sequence. The solvent used in the Soxhlet extraction was a mixed solvent of methanol and acetic acid in a volume ratio of 8:2. The Soxhlet extraction time was 5 hours and the temperature was 85°C. Finally, polystyrene microspheres were obtained.
[0174] (2) dispersing the polystyrene microspheres obtained in step (1) in an ethanol aqueous solution, wherein the mass ratio of the polystyrene microspheres to the ethanol aqueous solution is 1:20, and the volume ratio of ethanol to deionized water in the ethanol aqueous solution is 1:1.5, and ultrasonically dispersing at 300 W for 2 h to obtain a microsphere dispersion;
[0175] Adding 80 wt % concentrated sulfuric acid to the microsphere dispersion, wherein the mass ratio of polystyrene microspheres to concentrated sulfuric acid in the microsphere dispersion is 1:25, and ultrasonically dispersing at 400 W for 20 min to obtain a sulfonated microsphere solution, heating the sulfonated microsphere solution to 30° C. and stirring for 3 h, and filtering, washing and drying after the reaction to obtain sulfonated polystyrene microspheres;
[0176] Dopamine was dissolved in Tris-HCl buffer, and mixed evenly to obtain a dopamine solution with a concentration of 5 g / L and a pH value of 8; sulfonated polystyrene microspheres were dispersed in the dopamine solution, and the mass ratio of the sulfonated polystyrene microspheres to the dopamine in the dopamine solution was 1.5:1, and stirred at room temperature for 20 hours to allow dopamine to be in situ polymerized on the surface of the sulfonated polystyrene microspheres to form a polydopamine layer, and then filtered, washed and dried to obtain coated modified polystyrene microspheres;
[0177] (3) dispersing the carbon nanotubes in a mixed acid solution consisting of 17 mol / L concentrated sulfuric acid and 16 mol / L concentrated nitric acid, wherein the volume ratio of the concentrated sulfuric acid to the concentrated nitric acid in the mixed acid solution is 1:3, and the ratio of the carbon nanotubes to the mixed acid solution is 1 g:100 mL, and a first dispersion is obtained after ultrasonic dispersion, and the first dispersion is heated to 50° C. and stirred for 2 h, and then filtered, washed and dried to obtain the first carbon nanotubes;
[0178] Dispersing the first carbon nanotubes in an acidic hydrogen peroxide solution, wherein the acidic hydrogen peroxide solution includes glacial acetic acid, hydrogen peroxide solution and concentrated sulfuric acid in a volume ratio of 8:4:1, wherein the mass fraction of the hydrogen peroxide solution is 30wt%, the mass fraction of the concentrated sulfuric acid is 98wt%, and the ratio of the first carbon nanotubes to the acidic hydrogen peroxide solution is 1g:200mL, and the mixture is uniformly mixed to obtain a second dispersion; heating the second dispersion to 140°C under a protective atmosphere, and reacting at 1.2MPa for 40min, and obtaining second carbon nanotubes after the reaction is completed;
[0179] The second carbon nanotubes, polyethylene glycol 2000, polyvinyl pyrrolidone and deionized water are uniformly mixed to obtain a third dispersion, wherein the mass ratio of polyethylene glycol 2000 to polyvinyl pyrrolidone is 2:1, the ratio of the total mass of polyethylene glycol 2000 and polyvinyl pyrrolidone to the mass of the second carbon nanotubes is 1:1, and the mass fraction of the second carbon nanotubes in the third dispersion is 1wt%; an acid solution is added dropwise to the third dispersion to adjust the pH value of the third dispersion to 2, and the third dispersion is heated to 80° C. under a nitrogen atmosphere for reflux reaction for 5 hours, and after the reaction is completed, the modified carbon nanotubes are obtained by filtering, washing and drying;
[0180] (4) mixing the modified carbon nanotubes obtained in step (3), polyvinyl pyrrolidone and methanol, wherein the mass fraction of the modified carbon nanotubes in the carbon nanotube suspension is 20 wt %, and the ratio of the modified carbon nanotubes, polyvinyl pyrrolidone and methanol is 40 g:80 g:90 L, and after mixing, ultrasonically dispersing at 150 W for 60 min to obtain a carbon nanotube suspension;
[0181] Adding cobalt nitrate hexahydrate and nickel nitrate hexahydrate to a carbon nanotube suspension, wherein the mass ratio of the modified carbon nanotubes, cobalt nitrate hexahydrate and nickel nitrate hexahydrate is 1:20:40, and dispersing the mixture by ultrasonication at 300 W for 30 min to obtain a metal salt solution; adding the coated modified polystyrene microspheres obtained in step (2) to the metal salt solution, wherein the total mass of cobalt nitrate hexahydrate and nickel nitrate hexahydrate and the mass of the coated modified polystyrene microspheres is 2:1, and mixing the mixture to obtain a precursor solution; dissolving 2-methylimidazole in methanol, wherein the mass ratio of 2-methylimidazole to methanol is 1:20, and mixing the mixture to obtain an organic ligand solution;
[0182] The precursor solution and the organic ligand solution are uniformly mixed to obtain a carbon sphere precursor solution, wherein the total mass of cobalt nitrate hexahydrate and nickel nitrate hexahydrate in the precursor solution and the mass ratio of 2-methylimidazole in the organic ligand solution are 1:1.5; the carbon sphere precursor solution is heated to 160° C. for hydrothermal reaction for 24 hours, and the reaction product obtained by the reaction is washed, centrifuged and dried to obtain a hollow carbon sphere precursor, wherein the speed of centrifugation is 5000 r / min and the time is 5 minutes;
[0183] (5) Spread the hollow carbon sphere precursor obtained in step (4) in the first porcelain boat, spread the sodium hypophosphite in the second porcelain boat, and place the first porcelain boat and the second porcelain boat in a tubular furnace with a spacing of 10 cm, wherein the mass ratio of the hollow carbon sphere precursor to the sodium hypophosphite is 1:20;
[0184] A mixed gas of hydrogen and nitrogen with a volume ratio of 1:9 is introduced into the tubular furnace at a flow rate of 90 mL / min, and the pressure in the tubular furnace is 2 MPa, and the hollow carbon sphere precursor is subjected to a phosphating reaction. The phosphating reaction process includes: heating the hollow carbon sphere precursor to 300° C. at a heating rate of 4° C. / min and keeping the temperature for 80 min, cooling the hollow carbon sphere precursor to room temperature with the furnace to obtain a phosphide, and washing and drying the phosphide obtained by the reaction to obtain a phosphated hollow carbon sphere precursor;
[0185] Under a protective atmosphere, the phosphating hollow carbon sphere precursor was heated to 400°C at a heating rate of 3°C / min and kept at this temperature for 2 hours, then heated to 700°C at a heating rate of 5°C / min and kept at this temperature for 3 hours, and finally cooled to room temperature with the furnace to complete the carbonization treatment and obtain a hollow carbon sphere composite material;
[0186] (6) dispersing the hollow carbon sphere composite material obtained in step (5) in anhydrous ethanol, the ratio of the hollow carbon sphere composite material to anhydrous ethanol being 1 g:100 mL, and mixing them evenly to obtain a carbon sphere dispersion; dissolving ammonium molybdate and thiourea in anhydrous ethanol, the ratio of ammonium molybdate, thiourea and anhydrous ethanol being 1 g:2 g:80 mL, and mixing them evenly to obtain a MoS2 precursor solution;
[0187] The carbon sphere dispersion liquid is mixed with the MoS2 precursor solution, the mass ratio of the hollow carbon sphere composite material in the carbon sphere dispersion liquid to the ammonium molybdate in the MoS2 precursor solution is 1:1.5, and a reaction mixture is obtained after ultrasonic dispersion at 200 W for 40 minutes;
[0188] The reaction mixture is heated to 100°C at a heating rate of 2°C / min and kept warm for 5 hours. Subsequently, the reaction mixture is heated to 180°C at a heating rate of 1°C / min and kept warm for 8 hours. After the insulation is completed, it is cooled to room temperature with the furnace, so that ammonium molybdate and thiourea react to generate molybdenum disulfide nanosheets and load them on the surface of the hollow carbon ball composite material to obtain the highly conductive porous carbon material.
[0189] Figure 2 This is a scanning electron microscope image of the polystyrene microspheres prepared in this example. It can be seen from the image that a large number of pits appear on the surface of the polystyrene microspheres, and the specific surface area is increased.
[0190] Figure 3 The infrared spectra of the polystyrene microspheres and sulfonated polystyrene microspheres prepared in this example are shown in Figure 2. By comparison, the two infrared curves have a wavelength of 1610 cm -1 There are characteristic absorption peaks of benzene rings at all locations, while the infrared curve of sulfonated polystyrene microspheres is at 1175cm -1 The characteristic absorption peak at belongs to the stretching vibration peak of O=S=O, which indicates that sulfonic acid functional groups are successfully introduced into the polystyrene microspheres.
[0191] Figure 4 This is a scanning electron microscope image of untreated carbon nanotubes. Figure 5 is a scanning electron microscope image of the modified carbon nanotubes prepared in this example. Figure 4 It can be seen that the surface of the untreated carbon nanotubes has a small amount of protrusions and the tube wall is relatively intact. Figure 5 It can be seen that a large amount of filaments and a small amount of granular substances are attached to the surface of the modified carbon nanotubes. At the same time, the tube wall of the modified carbon nanotubes is damaged and pores are generated. The generation of these pores can greatly increase the specific surface area of the carbon nanotubes, which is beneficial to the loading of Ni / Co-MOF materials.
[0192] Figure 6 and Figure 7 The scanning electron microscope image and transmission electron microscope image of the composite porous material composed of modified carbon nanotubes and Ni / Co-MOF material prepared in this example are respectively Figure 6 It can be seen that after the introduction of modified carbon nanotubes, the spherical morphology of the stacked Ni / Co-MOF nanosheets disappeared, and an irregular network morphology connected by modified carbon nanotubes appeared, and the exposed modified carbon nanotubes could be clearly observed. Figure 7 It can be seen that the modified carbon nanotubes are embedded between the Ni / Co-MOF nanosheets, and the thin sheet-like Ni / Co-MOF material is distributed along the modified carbon nanotubes, and the material as a whole presents a highly porous structural feature.
[0193] Figure 8This is a scanning electron microscope image of the molybdenum disulfide nanosheets prepared in this embodiment. It can be seen from the figure that the molybdenum disulfide nanosheets are stacked on the carbon shell skeleton to form petal-shaped cluster microspheres, which is beneficial to further increase the specific surface area of the porous carbon material and provide more abundant channel paths for the transmission of electrolyte ions.
[0194] Example 2
[0195] This embodiment provides a method for preparing a highly conductive porous carbon material. Figure 1 As shown, the preparation method specifically comprises the following steps:
[0196] (1) Add polystyrene microsphere seeds with a particle size of 2.2 μm, dibutyl phthalate and toluene to a sodium dodecyl sulfate solution with a mass fraction of 0.22 wt%, wherein the ratio of polystyrene microsphere seeds, dibutyl phthalate, toluene and sodium dodecyl sulfate solution is 1 g:6 mL:16 mL:110 mL, and react for 22 h under mechanical stirring conditions of 420 rpm and heating in a water bath at 38 ° C to obtain a microsphere emulsion;
[0197] Add styrene monomer, divinylbenzene monomer and 2,2-azobisisobutyronitrile to a sodium dodecyl sulfate solution with a mass fraction of 0.22wt%, wherein the ratio of the total volume of the styrene monomer and the divinylbenzene monomer to the volume of the sodium dodecyl sulfate solution is 0.022:1, the volume ratio of the styrene monomer to the divinylbenzene monomer is 1:0.42, and the mass ratio of 2,2-azobisisobutyronitrile to the styrene monomer is 0.022:1, and mix well to obtain a microsphere precursor solution;
[0198] The microsphere precursor solution is added to the microsphere emulsion, the mass ratio of the styrene monomer in the microsphere precursor solution to the polystyrene microsphere seeds in the microsphere emulsion is 105:1, and the reaction precursor solution is obtained after being evenly mixed; a polyvinyl alcohol solution with a mass fraction of 10.5wt% is added to the reaction precursor solution, the mass ratio of the styrene monomer in the reaction precursor solution to the polyvinyl alcohol in the polyvinyl alcohol solution is 0.12:1, and the reaction solution is obtained after being evenly mixed;
[0199] The reaction solution was heated to 68°C in an anaerobic environment and stirred at 130 rpm for 28 hours. The reaction product was washed with deionized water, extracted with Soxhlet, washed with anhydrous ethanol, centrifuged and vacuum dried in sequence. The solvent used in the Soxhlet extraction was a mixed solvent of methanol and acetic acid in a volume ratio of 8.2:1.8. The Soxhlet extraction time was 6 hours and the temperature was 82°C. Finally, polystyrene microspheres were obtained.
[0200] (2) dispersing the polystyrene microspheres obtained in step (1) in an ethanol aqueous solution, wherein the mass ratio of the polystyrene microspheres to the ethanol aqueous solution is 1:22, and the volume ratio of ethanol to deionized water in the ethanol aqueous solution is 1:1.6, and ultrasonically dispersing at 320 W for 1.8 h to obtain a microsphere dispersion;
[0201] Adding concentrated sulfuric acid with a mass fraction of 82 wt % to the microsphere dispersion, the mass ratio of polystyrene microspheres to concentrated sulfuric acid in the microsphere dispersion is 1:24, and ultrasonically dispersing at 420 W for 18 min to obtain a sulfonated microsphere solution, heating the sulfonated microsphere solution to 32° C. and stirring for 2.8 h, filtering, washing and drying after the reaction to obtain sulfonated polystyrene microspheres;
[0202] Dopamine was dissolved in Tris-HCl buffer, and mixed evenly to obtain a dopamine solution with a concentration of 6 g / L and a pH value of 8.2; sulfonated polystyrene microspheres were dispersed in the dopamine solution, and the mass ratio of the sulfonated polystyrene microspheres to the dopamine in the dopamine solution was 1.8:1, and stirred at room temperature for 22 hours to allow dopamine to be in situ polymerized on the surface of the sulfonated polystyrene microspheres to form a polydopamine layer, and then filtered, washed and dried to obtain coated modified polystyrene microspheres;
[0203] (3) dispersing the carbon nanotubes in a mixed acid solution consisting of 17.2 mol / L concentrated sulfuric acid and 15.8 mol / L concentrated nitric acid, wherein the volume ratio of the concentrated sulfuric acid to the concentrated nitric acid in the mixed acid solution is 1:3.2, and the ratio of the carbon nanotubes to the mixed acid solution is 1 g:120 mL, and obtaining a first dispersion after ultrasonic dispersion, heating the first dispersion to 52° C. and stirring for 1.8 h, and then filtering, washing and drying to obtain the first carbon nanotubes;
[0204] Dispersing the first carbon nanotubes in an acidic hydrogen peroxide solution, wherein the acidic hydrogen peroxide solution includes glacial acetic acid, hydrogen peroxide solution and concentrated sulfuric acid in a volume ratio of 8.2:4.2:1, wherein the mass fraction of the hydrogen peroxide solution is 32wt%, the mass fraction of the concentrated sulfuric acid is 97wt%, and the ratio of the first carbon nanotubes to the acidic hydrogen peroxide solution is 1g:220mL, and the second dispersion is obtained after being uniformly mixed; heating the second dispersion to 142°C under a protective atmosphere, and reacting at 1.1MPa for 38min, and obtaining the second carbon nanotubes after the reaction is completed;
[0205] The second carbon nanotubes, polyethylene glycol 2000, polyvinyl pyrrolidone and deionized water are uniformly mixed to obtain a third dispersion, wherein the mass ratio of polyethylene glycol 2000 to polyvinyl pyrrolidone is 2.2:1, the ratio of the total mass of polyethylene glycol 2000 and polyvinyl pyrrolidone to the mass of the second carbon nanotubes is 1.2:1, and the mass fraction of the second carbon nanotubes in the third dispersion is 2wt%; an acid solution is added dropwise to the third dispersion to adjust the pH value of the third dispersion to 2.5, and the third dispersion is heated to 82° C. under a nitrogen atmosphere for reflux reaction for 4.5 hours, and after the reaction is completed, the modified carbon nanotubes are obtained by filtering, washing and drying;
[0206] (4) mixing the modified carbon nanotubes obtained in step (3), polyvinyl pyrrolidone and methanol, wherein the mass fraction of the modified carbon nanotubes in the carbon nanotube suspension is 22 wt %, and the ratio of the modified carbon nanotubes, polyvinyl pyrrolidone and methanol is 42 g:82 g:92 L, and after mixing, ultrasonically dispersing at 180 W for 58 min to obtain a carbon nanotube suspension;
[0207] Adding cobalt nitrate hexahydrate and nickel nitrate hexahydrate to a carbon nanotube suspension, wherein the mass ratio of the modified carbon nanotubes, cobalt nitrate hexahydrate and nickel nitrate hexahydrate is 1:22:42, and ultrasonically dispersing at 320 W for 28 minutes to obtain a metal salt solution; adding the coated modified polystyrene microspheres obtained in step (2) to the metal salt solution, wherein the total mass ratio of cobalt nitrate hexahydrate and nickel nitrate hexahydrate to the mass of the coated modified polystyrene microspheres is 2.2:1, and mixing them uniformly to obtain a precursor solution; dissolving 2-methylimidazole in methanol, wherein the mass ratio of 2-methylimidazole to methanol is 1:22, and mixing them uniformly to obtain an organic ligand solution;
[0208] The precursor solution and the organic ligand solution are uniformly mixed to obtain a carbon sphere precursor solution, wherein the total mass ratio of cobalt nitrate hexahydrate and nickel nitrate hexahydrate in the precursor solution to the mass ratio of 2-methylimidazole in the organic ligand solution is 1:1.6; the carbon sphere precursor solution is heated to 162° C. for hydrothermal reaction for 21 hours, and the reaction product obtained by the reaction is washed, centrifuged and dried to obtain a hollow carbon sphere precursor, wherein the speed of centrifugation is 5200 r / min and the time is 4.5 min;
[0209] (5) Spread the hollow carbon sphere precursor obtained in step (4) in the first porcelain boat, spread the sodium hypophosphite in the second porcelain boat, and place the first porcelain boat and the second porcelain boat in a tubular furnace with a spacing of 12 cm. The mass ratio of the hollow carbon sphere precursor to the sodium hypophosphite is 1:22.
[0210] A mixed gas of hydrogen and nitrogen with a volume ratio of 1.2:8.8 is introduced into the tubular furnace at a flow rate of 92 mL / min, and the pressure in the tubular furnace is 2.2 MPa, and the hollow carbon sphere precursor is subjected to a phosphating reaction. The phosphating reaction process includes: heating the hollow carbon sphere precursor to 320° C. at a heating rate of 4.2° C. / min and keeping the temperature for 78 min, cooling the hollow carbon sphere precursor to room temperature with the furnace to obtain a phosphide, and washing and drying the phosphide obtained by the reaction to obtain a phosphated hollow carbon sphere precursor;
[0211] Under a protective atmosphere, the phosphating hollow carbon sphere precursor was heated to 420°C at a heating rate of 3.2°C / min and kept at this temperature for 1.8h, then heated to 720°C at a heating rate of 5.2°C / min and kept at this temperature for 2.8h, and finally cooled to room temperature in the furnace to complete the carbonization treatment and obtain a hollow carbon sphere composite material.
[0212] (6) dispersing the hollow carbon sphere composite material obtained in step (5) in anhydrous ethanol, the ratio of the hollow carbon sphere composite material to anhydrous ethanol being 1 g:120 mL, and mixing them evenly to obtain a carbon sphere dispersion; dissolving ammonium molybdate and thiourea in anhydrous ethanol, the ratio of ammonium molybdate, thiourea and anhydrous ethanol being 1 g:2.2 g:82 mL, and mixing them evenly to obtain a MoS2 precursor solution;
[0213] The carbon sphere dispersion liquid was mixed with the MoS2 precursor solution, the mass ratio of the hollow carbon sphere composite material in the carbon sphere dispersion liquid to the ammonium molybdate in the MoS2 precursor solution was 1:1.8, and a reaction mixture was obtained after ultrasonic dispersion at 220 W for 38 minutes;
[0214] The reaction mixture was heated to 105°C at a heating rate of 2.2°C / min and kept warm for 4.8 hours. Subsequently, the reaction mixture was heated to 185°C at a heating rate of 1.2°C / min and kept warm for 7.5 hours. After the insulation, it was cooled to room temperature in the furnace, so that ammonium molybdate and thiourea reacted to generate molybdenum disulfide nanosheets and loaded on the surface of the hollow carbon ball composite material to obtain the highly conductive porous carbon material.
[0215] Example 3
[0216] This embodiment provides a method for preparing a highly conductive porous carbon material. Figure 1 As shown, the preparation method specifically comprises the following steps:
[0217] (1) Add polystyrene microsphere seeds with a particle size of 2.5 μm, dibutyl phthalate and toluene to a sodium dodecyl sulfate solution with a mass fraction of 0.25 wt%, wherein the ratio of polystyrene microsphere seeds, dibutyl phthalate, toluene and sodium dodecyl sulfate solution is 1 g:7 mL:17 mL:120 mL, and react for 25 h under mechanical stirring conditions at 450 rpm and heating in a water bath at 35 °C to obtain a microsphere emulsion;
[0218] Add styrene monomer, divinylbenzene monomer and 2,2-azobisisobutyronitrile to a sodium dodecyl sulfate solution, wherein the ratio of the total volume of the styrene monomer and the divinylbenzene monomer to the volume of the sodium dodecyl sulfate solution is 0.025:1, the volume ratio of the styrene monomer to the divinylbenzene monomer is 1:0.45, and the mass ratio of 2,2-azobisisobutyronitrile to the styrene monomer is 0.025:1, and mix well to obtain a microsphere precursor solution;
[0219] The microsphere precursor solution is added to the microsphere emulsion, the mass ratio of the styrene monomer in the microsphere precursor solution to the polystyrene microsphere seeds in the microsphere emulsion is 110:1, and the reaction precursor solution is obtained after being evenly mixed; a polyvinyl alcohol solution with a mass fraction of 11wt% is added to the reaction precursor solution, the mass ratio of the styrene monomer in the reaction precursor solution to the polyvinyl alcohol in the polyvinyl alcohol solution is 0.15:1, and the reaction solution is obtained after being evenly mixed;
[0220] The reaction solution was heated to 70°C in an anaerobic environment and stirred at 120 rpm for 25 hours. The reaction product was washed with deionized water, extracted with Soxhlet, washed with anhydrous ethanol, centrifuged and vacuum dried in sequence. The solvent used in the Soxhlet extraction was a mixed solvent of methanol and acetic acid in a volume ratio of 8.5:1.5. The Soxhlet extraction time was 7 hours and the temperature was 80°C, and polystyrene microspheres were finally obtained.
[0221] (2) dispersing the polystyrene microspheres obtained in step (1) in an ethanol aqueous solution, wherein the mass ratio of the polystyrene microspheres to the ethanol aqueous solution is 1:25, and the volume ratio of ethanol to deionized water in the ethanol aqueous solution is 1:1.7, and ultrasonically dispersing at 350 W for 1.5 h to obtain a microsphere dispersion;
[0222] Adding concentrated sulfuric acid with a mass fraction of 85 wt % to the microsphere dispersion, the mass ratio of polystyrene microspheres to concentrated sulfuric acid in the microsphere dispersion is 1:22, and ultrasonically dispersing at 450 W for 15 min to obtain a sulfonated microsphere solution, heating the sulfonated microsphere solution to 35° C. and stirring for 2.5 h, filtering, washing and drying after the reaction to obtain sulfonated polystyrene microspheres;
[0223] Dopamine was dissolved in Tris-HCl buffer, and mixed evenly to obtain a dopamine solution with a concentration of 7 g / L and a pH value of 8.5; sulfonated polystyrene microspheres were dispersed in the dopamine solution, and the mass ratio of the sulfonated polystyrene microspheres to the dopamine in the dopamine solution was 2:1, and stirred at room temperature for 25 hours to allow dopamine to be in situ polymerized on the surface of the sulfonated polystyrene microspheres to form a polydopamine layer, and then filtered, washed and dried to obtain coated modified polystyrene microspheres;
[0224] (3) dispersing the carbon nanotubes in a mixed acid solution consisting of 17.5 mol / L concentrated sulfuric acid and 15.5 mol / L concentrated nitric acid, wherein the volume ratio of the concentrated sulfuric acid to the concentrated nitric acid in the mixed acid solution is 1:3.5, and the ratio of the carbon nanotubes to the mixed acid solution is 1 g:150 mL, and a first dispersion is obtained after ultrasonic dispersion. The first dispersion is heated to 55° C. and stirred for 1.5 h, and then filtered, washed and dried to obtain the first carbon nanotubes;
[0225] Dispersing the first carbon nanotubes in an acidic hydrogen peroxide solution, wherein the acidic hydrogen peroxide solution includes glacial acetic acid, a hydrogen peroxide solution, and concentrated sulfuric acid in a volume ratio of 8.5:4.5:1, wherein the mass fraction of the hydrogen peroxide solution is 35wt%, the mass fraction of the concentrated sulfuric acid is 97wt%, and the ratio of the first carbon nanotubes to the acidic hydrogen peroxide solution is 1g:250mL, and the mixture is uniformly mixed to obtain a second dispersion; heating the second dispersion to 145°C under a protective atmosphere, and reacting at 1MPa for 35min, and obtaining second carbon nanotubes after the reaction is completed;
[0226] The second carbon nanotubes, polyethylene glycol 2000, polyvinyl pyrrolidone and deionized water are uniformly mixed to obtain a third dispersion, wherein the mass ratio of polyethylene glycol 2000 to polyvinyl pyrrolidone is 2.5:1, the ratio of the total mass of polyethylene glycol 2000 and polyvinyl pyrrolidone to the mass of the second carbon nanotubes is 1.5:1, and the mass fraction of the second carbon nanotubes in the third dispersion is 3wt%; an acid solution is added dropwise to the third dispersion to adjust the pH value of the third dispersion to 3, and the third dispersion is heated to 85° C. under a nitrogen atmosphere for reflux reaction for 4 hours, and after the reaction is completed, the modified carbon nanotubes are obtained by filtering, washing and drying;
[0227] (4) mixing the modified carbon nanotubes obtained in step (3), polyvinyl pyrrolidone and methanol, wherein the mass fraction of the modified carbon nanotubes in the carbon nanotube suspension is 25 wt %, and the ratio of the modified carbon nanotubes, polyvinyl pyrrolidone and methanol is 45 g:85 g:95 L, and after mixing, ultrasonically dispersing at 200 W for 55 min to obtain a carbon nanotube suspension;
[0228] Adding cobalt nitrate hexahydrate and nickel nitrate hexahydrate to a carbon nanotube suspension, wherein the mass ratio of the modified carbon nanotubes, cobalt nitrate hexahydrate and nickel nitrate hexahydrate is 1:25:45, and dispersing the mixture ultrasonically at 350 W for 25 min to obtain a metal salt solution; adding the coated modified polystyrene microspheres obtained in step (2) to the metal salt solution, wherein the total mass ratio of cobalt nitrate hexahydrate and nickel nitrate hexahydrate to the mass of the coated modified polystyrene microspheres is 2.5:1, and mixing the mixture evenly to obtain a precursor solution; dissolving 2-methylimidazole in methanol, wherein the mass ratio of 2-methylimidazole to methanol is 1:25, and mixing the mixture evenly to obtain an organic ligand solution;
[0229] The precursor solution and the organic ligand solution are uniformly mixed to obtain a carbon sphere precursor solution, wherein the total mass of cobalt nitrate hexahydrate and nickel nitrate hexahydrate in the precursor solution and the mass ratio of 2-methylimidazole in the organic ligand solution is 1:1.7; the carbon sphere precursor solution is heated to 165° C. for hydrothermal reaction for 18 hours, and the reaction product obtained by the reaction is washed, centrifuged and dried to obtain a hollow carbon sphere precursor, wherein the speed of centrifugation is 5500 r / min and the time is 4 minutes;
[0230] (5) Spread the hollow carbon sphere precursor obtained in step (4) in the first porcelain boat, spread the sodium hypophosphite in the second porcelain boat, and place the first porcelain boat and the second porcelain boat in a tubular furnace with a spacing of 15 cm, wherein the mass ratio of the hollow carbon sphere precursor to the sodium hypophosphite is 1:25;
[0231] A mixed gas of hydrogen and nitrogen with a volume ratio of 1.5:8.5 is introduced into the tubular furnace at a flow rate of 95 mL / min, and the pressure in the tubular furnace is 2.5 MPa, and the hollow carbon sphere precursor is subjected to a phosphating reaction. The phosphating reaction process includes: heating the hollow carbon sphere precursor to 350° C. at a heating rate of 4.5° C. / min and keeping the temperature for 75 min, cooling the hollow carbon sphere precursor to room temperature with the furnace to obtain a phosphide, and washing and drying the phosphide obtained by the reaction to obtain a phosphated hollow carbon sphere precursor;
[0232] Under a protective atmosphere, the phosphating hollow carbon sphere precursor was heated to 450°C at a heating rate of 3.5°C / min and kept at this temperature for 1.5 h, then heated to 750°C at a heating rate of 5.5°C / min and kept at this temperature for 2.5 h, and finally cooled to room temperature in the furnace to complete the carbonization treatment, thereby obtaining a hollow carbon sphere composite material.
[0233] (6) dispersing the hollow carbon sphere composite material obtained in step (5) in anhydrous ethanol, the ratio of the hollow carbon sphere composite material to anhydrous ethanol being 1 g:150 mL, and mixing them evenly to obtain a carbon sphere dispersion; dissolving ammonium molybdate and thiourea in anhydrous ethanol, the ratio of ammonium molybdate, thiourea and anhydrous ethanol being 1 g:2.5 g:85 mL, and mixing them evenly to obtain a MoS2 precursor solution;
[0234] The carbon sphere dispersion liquid is mixed with the MoS2 precursor solution, the mass ratio of the hollow carbon sphere composite material in the carbon sphere dispersion liquid to the ammonium molybdate in the MoS2 precursor solution is 1:2, and a reaction mixture is obtained after ultrasonic dispersion at 250 W for 35 minutes;
[0235] The reaction mixture was heated to 110°C at a heating rate of 2.5°C / min and kept warm for 4.5 hours. Subsequently, the reaction mixture was heated to 190°C at a heating rate of 1.5°C / min and kept warm for 7 hours. After the insulation, it was cooled to room temperature in the furnace, so that ammonium molybdate and thiourea reacted to generate molybdenum disulfide nanosheets and loaded on the surface of the hollow carbon ball composite material to obtain the highly conductive porous carbon material.
[0236] Example 4
[0237] This embodiment provides a method for preparing a highly conductive porous carbon material. Figure 1 As shown, the preparation method specifically comprises the following steps:
[0238] (1) Add polystyrene microsphere seeds with a particle size of 2.8 μm, dibutyl phthalate and toluene to a sodium dodecyl sulfate solution with a mass fraction of 0.28 wt%, wherein the ratio of polystyrene microsphere seeds, dibutyl phthalate, toluene and sodium dodecyl sulfate solution is 1 g:8 mL:18 mL:130 mL, and react for 28 h under mechanical stirring conditions of 480 rpm and heating in a water bath at 32 °C to obtain a microsphere emulsion;
[0239] Add styrene monomer, divinylbenzene monomer and 2,2-azobisisobutyronitrile to a sodium dodecyl sulfate solution with a mass fraction of 0.28wt%, wherein the ratio of the total volume of the styrene monomer and the divinylbenzene monomer to the volume of the sodium dodecyl sulfate solution is 0.028:1, the volume ratio of the styrene monomer to the divinylbenzene monomer is 1:0.48, and the mass ratio of 2,2-azobisisobutyronitrile to the styrene monomer is 0.028:1, and mix well to obtain a microsphere precursor solution;
[0240] The microsphere precursor solution is added to the microsphere emulsion, the mass ratio of the styrene monomer in the microsphere precursor solution to the polystyrene microsphere seeds in the microsphere emulsion is 115:1, and the reaction precursor solution is obtained after being evenly mixed; a polyvinyl alcohol solution with a mass fraction of 11.5wt% is added to the reaction precursor solution, the mass ratio of the styrene monomer in the reaction precursor solution to the polyvinyl alcohol in the polyvinyl alcohol solution is 0.18:1, and the reaction solution is obtained after being evenly mixed;
[0241] The reaction solution was heated to 72°C in an anaerobic environment and stirred at 110 rpm for 22 hours. The reaction product was washed with deionized water, extracted with Soxhlet, washed with anhydrous ethanol, centrifuged and vacuum dried in sequence. The solvent used in the Soxhlet extraction was a mixed solvent of methanol and acetic acid in a volume ratio of 8.8:1.2. The Soxhlet extraction time was 8 hours and the temperature was 78°C. Finally, polystyrene microspheres were obtained.
[0242] (2) dispersing the polystyrene microspheres obtained in step (1) in an ethanol aqueous solution, wherein the mass ratio of the polystyrene microspheres to the ethanol aqueous solution is 1:28, and the volume ratio of ethanol to deionized water in the ethanol aqueous solution is 1:1.8, and ultrasonically dispersing at 380 W for 1.2 h to obtain a microsphere dispersion;
[0243] Adding concentrated sulfuric acid with a mass fraction of 88 wt % to the microsphere dispersion, the mass ratio of polystyrene microspheres to concentrated sulfuric acid in the microsphere dispersion is 1:21, and ultrasonically dispersing at 480 W for 12 min to obtain a sulfonated microsphere solution, heating the sulfonated microsphere solution to 38° C. and stirring for reaction for 2.2 h, and filtering, washing and drying after the reaction to obtain sulfonated polystyrene microspheres;
[0244] Dopamine was dissolved in Tris-HCl buffer, and mixed evenly to obtain a dopamine solution with a concentration of 7 g / L and a pH value of 8.8; sulfonated polystyrene microspheres were dispersed in the dopamine solution, and the mass ratio of the sulfonated polystyrene microspheres to the dopamine in the dopamine solution was 2.2:1, and stirred at room temperature for 28 hours to allow dopamine to be in situ polymerized on the surface of the sulfonated polystyrene microspheres to form a polydopamine layer, and then filtered, washed and dried to obtain coated modified polystyrene microspheres;
[0245] (3) dispersing the carbon nanotubes in a mixed acid solution consisting of 17.8 mol / L concentrated sulfuric acid and 15.2 mol / L concentrated nitric acid, wherein the volume ratio of the concentrated sulfuric acid to the concentrated nitric acid in the mixed acid solution is 1:3.8, and the ratio of the carbon nanotubes to the mixed acid solution is 1 g:180 mL, and obtaining a first dispersion after ultrasonic dispersion, heating the first dispersion to 58° C. and stirring for 1.2 h, and then filtering, washing and drying to obtain the first carbon nanotubes;
[0246] Dispersing the first carbon nanotubes in an acidic hydrogen peroxide solution, wherein the acidic hydrogen peroxide solution includes glacial acetic acid, a hydrogen peroxide solution, and concentrated sulfuric acid in a volume ratio of 8.8:4.8:1, wherein the mass fraction of the hydrogen peroxide solution is 38wt%, the mass fraction of the concentrated sulfuric acid is 96wt%, and the ratio of the first carbon nanotubes to the acidic hydrogen peroxide solution is 1g:280mL, and the second dispersion is obtained after being uniformly mixed; heating the second dispersion to 148°C under a protective atmosphere, and reacting at 0.9MPa for 32min, and obtaining the second carbon nanotubes after the reaction is completed;
[0247] The second carbon nanotubes, polyethylene glycol 2000, polyvinyl pyrrolidone and deionized water are uniformly mixed to obtain a third dispersion, wherein the mass ratio of polyethylene glycol 2000 to polyvinyl pyrrolidone is 2.8:1, the ratio of the total mass of polyethylene glycol 2000 and polyvinyl pyrrolidone to the mass of the second carbon nanotubes is 1.8:1, and the mass fraction of the second carbon nanotubes in the third dispersion is 4wt%; an acid solution is added dropwise to the third dispersion to adjust the pH value of the third dispersion to 3.5, and the third dispersion is heated to 88° C. under a nitrogen atmosphere for reflux reaction for 3.5 hours, and after the reaction is completed, the modified carbon nanotubes are obtained by filtering, washing and drying;
[0248] (4) mixing the modified carbon nanotubes obtained in step (3), polyvinyl pyrrolidone and methanol, wherein the mass fraction of the modified carbon nanotubes in the carbon nanotube suspension is 28wt%, and the ratio of the modified carbon nanotubes, polyvinyl pyrrolidone and methanol is 48g:88g:98L, and after mixing, ultrasonically dispersing at 220W for 52min to obtain a carbon nanotube suspension;
[0249] Adding cobalt nitrate hexahydrate and nickel nitrate hexahydrate to the carbon nanotube suspension, wherein the mass ratio of the modified carbon nanotubes, cobalt nitrate hexahydrate and nickel nitrate hexahydrate is 1:28:48, and ultrasonically dispersing at 380 W for 22 min to obtain a metal salt solution; adding the coated modified polystyrene microspheres obtained in step (2) to the metal salt solution, wherein the total mass ratio of cobalt nitrate hexahydrate and nickel nitrate hexahydrate to the mass of the coated modified polystyrene microspheres is 2.8:1, and mixing them uniformly to obtain a precursor solution; dissolving 2-methylimidazole in methanol, wherein the mass ratio of 2-methylimidazole to methanol is 1:28, and mixing them uniformly to obtain an organic ligand solution;
[0250] The precursor solution and the organic ligand solution are uniformly mixed to obtain a carbon sphere precursor solution, wherein the total mass ratio of cobalt nitrate hexahydrate and nickel nitrate hexahydrate in the precursor solution to the mass ratio of 2-methylimidazole in the organic ligand solution is 1:1.8; the carbon sphere precursor solution is heated to 168° C. for hydrothermal reaction for 15 hours, and the reaction product obtained by the reaction is washed, centrifuged and dried to obtain a hollow carbon sphere precursor, wherein the speed of centrifugation is 5800 r / min and the time is 3.5 min;
[0251] (5) Spread the hollow carbon sphere precursor obtained in step (4) in the first porcelain boat, spread the sodium hypophosphite in the second porcelain boat, and place the first porcelain boat and the second porcelain boat in a tubular furnace with an interval of 18 cm, wherein the mass ratio of the hollow carbon sphere precursor to the sodium hypophosphite is 1:28;
[0252] A mixed gas of hydrogen and nitrogen with a volume ratio of 1.8:8.2 is introduced into the tubular furnace at a flow rate of 98 mL / min, and the pressure in the tubular furnace is 2.8 MPa, and the hollow carbon sphere precursor is subjected to a phosphating reaction. The phosphating reaction process includes: heating the hollow carbon sphere precursor to 380° C. at a heating rate of 4.8° C. / min and keeping the temperature for 72 minutes, cooling the furnace to room temperature to obtain a phosphide, and washing and drying the phosphide obtained by the reaction to obtain a phosphated hollow carbon sphere precursor;
[0253] Under a protective atmosphere, the phosphating hollow carbon sphere precursor was heated to 480°C at a heating rate of 3.8°C / min and kept at this temperature for 1.2 h, then heated to 780°C at a heating rate of 5.8°C / min and kept at this temperature for 2.2 h, and finally cooled to room temperature in the furnace to complete the carbonization treatment and obtain a hollow carbon sphere composite material.
[0254] (6) dispersing the hollow carbon sphere composite material obtained in step (5) in anhydrous ethanol, the ratio of the hollow carbon sphere composite material to anhydrous ethanol being 1 g:180 mL, and mixing them evenly to obtain a carbon sphere dispersion; dissolving ammonium molybdate and thiourea in anhydrous ethanol, the ratio of ammonium molybdate, thiourea and anhydrous ethanol being 1 g:2.8 g:88 mL, and mixing them evenly to obtain a MoS2 precursor solution;
[0255] The carbon sphere dispersion liquid was mixed with the MoS2 precursor solution, the mass ratio of the hollow carbon sphere composite material in the carbon sphere dispersion liquid to the ammonium molybdate in the MoS2 precursor solution was 1:2.2, and a reaction mixture was obtained after ultrasonic dispersion at 280 W for 32 minutes;
[0256] The reaction mixture was heated to 115°C at a heating rate of 2.8°C / min and kept warm for 4.2 hours. Subsequently, the reaction mixture was heated to 195°C at a heating rate of 1.8°C / min and kept warm for 6.5 hours. After the insulation, it was cooled to room temperature in the furnace, so that ammonium molybdate and thiourea reacted to generate molybdenum disulfide nanosheets and loaded on the surface of the hollow carbon ball composite material to obtain the highly conductive porous carbon material.
[0257] Example 5
[0258] This embodiment provides a method for preparing a highly conductive porous carbon material. Figure 1 As shown, the preparation method specifically comprises the following steps:
[0259] (1) Add polystyrene microsphere seeds with a particle size of 3 μm, dibutyl phthalate and toluene to a sodium dodecyl sulfate solution with a mass fraction of 0.3 wt%, wherein the ratio of polystyrene microsphere seeds, dibutyl phthalate, toluene and sodium dodecyl sulfate solution is 1 g:10 mL:20 mL:150 mL, and react for 30 h under mechanical stirring conditions at 500 rpm and heating in a water bath at 30°C to obtain a microsphere emulsion;
[0260] Add styrene monomer, divinylbenzene monomer and 2,2-azobisisobutyronitrile to a sodium dodecyl sulfate solution with a mass fraction of 0.3wt%, wherein the ratio of the total volume of the styrene monomer and the divinylbenzene monomer to the volume of the sodium dodecyl sulfate solution is 0.03:1, the volume ratio of the styrene monomer to the divinylbenzene monomer is 1:0.5, and the mass ratio of 2,2-azobisisobutyronitrile to the styrene monomer is 0.03:1, and mix well to obtain a microsphere precursor solution;
[0261] The microsphere precursor solution is added to the microsphere emulsion, the mass ratio of the styrene monomer in the microsphere precursor solution to the polystyrene microsphere seeds in the microsphere emulsion is 120:1, and the reaction precursor solution is obtained after being evenly mixed; a polyvinyl alcohol solution with a mass fraction of 12wt% is added to the reaction precursor solution, the mass ratio of the styrene monomer in the reaction precursor solution to the polyvinyl alcohol in the polyvinyl alcohol solution is 0.2:1, and the reaction solution is obtained after being evenly mixed;
[0262] The reaction solution was heated to 75°C in an anaerobic environment and stirred at 100 rpm for 20 hours. The reaction product was washed with deionized water, extracted with Soxhlet, washed with anhydrous ethanol, centrifuged and vacuum dried in sequence. The solvent used in the Soxhlet extraction was a mixed solvent of methanol and acetic acid in a volume ratio of 9:1. The Soxhlet extraction time was 10 hours and the temperature was 75°C, and polystyrene microspheres were finally obtained.
[0263] (2) dispersing the polystyrene microspheres obtained in step (1) in an ethanol aqueous solution, wherein the mass ratio of the polystyrene microspheres to the ethanol aqueous solution is 1:30, and the volume ratio of ethanol to deionized water in the ethanol aqueous solution is 1:2, and ultrasonically dispersing at 400 W for 1 h to obtain a microsphere dispersion;
[0264] Adding concentrated sulfuric acid with a mass fraction of 90 wt % to the microsphere dispersion, the mass ratio of polystyrene microspheres to concentrated sulfuric acid in the microsphere dispersion is 1:20, and ultrasonically dispersing at 500 W for 10 min to obtain a sulfonated microsphere solution, heating the sulfonated microsphere solution to 40° C. and stirring for 2 h, and filtering, washing and drying after the reaction to obtain sulfonated polystyrene microspheres;
[0265] Dopamine was dissolved in Tris-HCl buffer, and mixed evenly to obtain a dopamine solution with a concentration of 8 g / L and a pH value of 9; sulfonated polystyrene microspheres were dispersed in the dopamine solution, and the mass ratio of the sulfonated polystyrene microspheres to the dopamine in the dopamine solution was 2.5:1, and stirred at room temperature for 30 hours to allow dopamine to be in situ polymerized on the surface of the sulfonated polystyrene microspheres to form a polydopamine layer, and then filtered, washed and dried to obtain coated modified polystyrene microspheres;
[0266] (3) dispersing the carbon nanotubes in a mixed acid solution consisting of 18 mol / L concentrated sulfuric acid and 15 mol / L concentrated nitric acid, wherein the volume ratio of the concentrated sulfuric acid to the concentrated nitric acid in the mixed acid solution is 1:4, and the ratio of the carbon nanotubes to the mixed acid solution is 1 g:200 mL, and a first dispersion is obtained after ultrasonic dispersion, and the first dispersion is heated to 60° C. and stirred for 1 h, and then filtered, washed and dried to obtain the first carbon nanotubes;
[0267] Dispersing the first carbon nanotubes in an acidic hydrogen peroxide solution, wherein the acidic hydrogen peroxide solution includes glacial acetic acid, hydrogen peroxide solution and concentrated sulfuric acid in a volume ratio of 9:5:1, wherein the mass fraction of the hydrogen peroxide solution is 40wt%, the mass fraction of the concentrated sulfuric acid is 95wt%, and the ratio of the first carbon nanotubes to the acidic hydrogen peroxide solution is 1g:300mL, and the mixture is uniformly mixed to obtain a second dispersion; heating the second dispersion to 150°C under a protective atmosphere, and reacting at 0.8MPa for 30min, and obtaining second carbon nanotubes after the reaction is completed;
[0268] The second carbon nanotubes, polyethylene glycol 2000, polyvinyl pyrrolidone and deionized water are uniformly mixed to obtain a third dispersion, wherein the mass ratio of polyethylene glycol 2000 to polyvinyl pyrrolidone is 3:1, the ratio of the total mass of polyethylene glycol 2000 and polyvinyl pyrrolidone to the mass of the second carbon nanotubes is 2:1, and the mass fraction of the second carbon nanotubes in the third dispersion is 5wt%; an acid solution is added dropwise to the third dispersion to adjust the pH value of the third dispersion to 4, and the third dispersion is heated to 90° C. under a nitrogen atmosphere for reflux reaction for 3 hours, and after the reaction is completed, the modified carbon nanotubes are obtained by filtering, washing and drying;
[0269] (4) mixing the modified carbon nanotubes obtained in step (3), polyvinyl pyrrolidone and methanol, wherein the mass fraction of the modified carbon nanotubes in the carbon nanotube suspension is 30 wt %, and the ratio of the modified carbon nanotubes, polyvinyl pyrrolidone and methanol is 50 g:90 g:100 L, and after mixing, ultrasonically dispersing at 250 W for 50 min to obtain a carbon nanotube suspension;
[0270] Adding cobalt nitrate hexahydrate and nickel nitrate hexahydrate to a carbon nanotube suspension, wherein the mass ratio of the modified carbon nanotubes, cobalt nitrate hexahydrate and nickel nitrate hexahydrate is 1:30:50, and dispersing the mixture by ultrasonication at 400 W for 20 min to obtain a metal salt solution; adding the coated modified polystyrene microspheres obtained in step (2) to the metal salt solution, wherein the total mass of cobalt nitrate hexahydrate and nickel nitrate hexahydrate and the mass of the coated modified polystyrene microspheres is 3:1, and mixing the mixture to obtain a precursor solution; dissolving 2-methylimidazole in methanol, wherein the mass ratio of 2-methylimidazole to methanol is 1:30, and mixing the mixture to obtain an organic ligand solution;
[0271] The precursor solution and the organic ligand solution are uniformly mixed to obtain a carbon sphere precursor solution, wherein the total mass of cobalt nitrate hexahydrate and nickel nitrate hexahydrate in the precursor solution and the mass ratio of 2-methylimidazole in the organic ligand solution is 1:2; the carbon sphere precursor solution is heated to 170° C. for hydrothermal reaction for 12 hours, and the reaction product obtained by the reaction is washed, centrifuged and dried to obtain a hollow carbon sphere precursor, wherein the speed of centrifugation is 6000 r / min and the time is 3 minutes;
[0272] (5) Spread the hollow carbon sphere precursor obtained in step (4) in the first porcelain boat, spread the sodium hypophosphite in the second porcelain boat, and place the first porcelain boat and the second porcelain boat in a tubular furnace with a spacing of 20 cm, wherein the mass ratio of the hollow carbon sphere precursor to the sodium hypophosphite is 1:30;
[0273] A mixed gas of hydrogen and nitrogen with a volume ratio of 2:8 is introduced into the tubular furnace at a flow rate of 100 mL / min, and the pressure in the tubular furnace is 3 MPa, and the hollow carbon sphere precursor is subjected to a phosphating reaction. The phosphating reaction process includes: heating the hollow carbon sphere precursor to 400°C at a heating rate of 5°C / min and keeping the temperature for 70 minutes, cooling the furnace to room temperature to obtain a phosphide, and washing and drying the phosphide obtained by the reaction to obtain a phosphated hollow carbon sphere precursor;
[0274] Under a protective atmosphere, the phosphating hollow carbon sphere precursor was heated to 500°C at a heating rate of 4°C / min and kept at this temperature for 1 hour, then heated to 800°C at a heating rate of 6°C / min and kept at this temperature for 2 hours, and finally cooled to room temperature in the furnace to complete the carbonization treatment and obtain a hollow carbon sphere composite material.
[0275] (6) dispersing the hollow carbon sphere composite material obtained in step (5) in anhydrous ethanol, the ratio of the hollow carbon sphere composite material to anhydrous ethanol being 1 g: 200 mL, and mixing them evenly to obtain a carbon sphere dispersion; dissolving ammonium molybdate and thiourea in anhydrous ethanol, the ratio of ammonium molybdate, thiourea and anhydrous ethanol being 1 g: 3 g: 90 mL, and mixing them evenly to obtain a MoS2 precursor solution;
[0276] The carbon sphere dispersion liquid was mixed with the MoS2 precursor solution, the mass ratio of the hollow carbon sphere composite material in the carbon sphere dispersion liquid to the ammonium molybdate in the MoS2 precursor solution was 1:2.5, and a reaction mixture was obtained after ultrasonic dispersion at 300 W for 30 minutes;
[0277] The reaction mixture is heated to 120°C at a heating rate of 3°C / min and kept warm for 4 hours. Subsequently, the reaction mixture is heated to 200°C at a heating rate of 2°C / min and kept warm for 6 hours. After the insulation, it is cooled to room temperature with the furnace, so that ammonium molybdate and thiourea react to generate molybdenum disulfide nanosheets and load them on the surface of the hollow carbon ball composite material to obtain the highly conductive porous carbon material.
[0278] Comparative Example 1
[0279] This comparative example provides a method for preparing a highly conductive porous carbon material. The difference from Example 1 is that in step (2), the mass ratio of sulfonated polystyrene microspheres to dopamine in the dopamine solution is adjusted to 1.2:1, and the other operating parameters and process steps are exactly the same as those in Example 1.
[0280] Comparative Example 2
[0281] This comparative example provides a method for preparing a highly conductive porous carbon material. The difference from Example 1 is that in step (2), the mass ratio of sulfonated polystyrene microspheres to dopamine in the dopamine solution is adjusted to 2.8:1, and the other operating parameters and process steps are exactly the same as those in Example 1.
[0282] Comparative Example 3
[0283] This comparative example provides a method for preparing a highly conductive porous carbon material. The difference from Example 1 is that in step (4), the mass ratio of the modified carbon nanotubes, cobalt nitrate hexahydrate and nickel nitrate hexahydrate in the carbon nanotube suspension is adjusted to 1:15:35, and the other operating parameters and process steps are exactly the same as those in Example 1.
[0284] Comparative Example 4
[0285] This comparative example provides a method for preparing a highly conductive porous carbon material. The difference from Example 1 is that in step (4), the mass ratio of the modified carbon nanotubes, cobalt nitrate hexahydrate and nickel nitrate hexahydrate in the carbon nanotube suspension is adjusted to 1:35:55, and the other operating parameters and process steps are exactly the same as those in Example 1.
[0286] Comparative Example 5
[0287] This comparative example provides a method for preparing a highly conductive porous carbon material. The difference from Example 1 is that in step (4), the temperature of the hydrothermal reaction of the carbon sphere precursor solution is adjusted to 150° C., and the other operating parameters and process steps are exactly the same as those in Example 1.
[0288] Comparative Example 6
[0289] This comparative example provides a method for preparing a highly conductive porous carbon material. The difference from Example 1 is that in step (4), the temperature of the hydrothermal reaction of the carbon sphere precursor solution is adjusted to 180° C., and the other operating parameters and process steps are exactly the same as those in Example 1.
[0290] Comparative Example 7
[0291] This comparative example provides a method for preparing a highly conductive porous carbon material. The difference from Example 1 is that in step (6), the mass ratio of the hollow carbon sphere composite material to ammonium molybdate in the MoS2 precursor solution is adjusted to 1:1, and the other operating parameters and process steps are exactly the same as those in Example 1.
[0292] Comparative Example 8
[0293] This comparative example provides a method for preparing a highly conductive porous carbon material. The difference from Example 1 is that in step (6), the mass ratio of the hollow carbon sphere composite material to ammonium molybdate in the MoS2 precursor solution is adjusted to 1:3, and the other operating parameters and process steps are exactly the same as those in Example 1.
[0294] The electrochemical properties of the porous carbon materials prepared in Examples 1-5 and Comparative Examples 1-8 were tested, and the specific test steps are as follows:
[0295] (1) Preparation of electrodes
[0296] The porous carbon material, carbon black and polytetrafluoroethylene prepared in Examples 1-5 and Comparative Examples 1-8 were placed in a mortar at a mass ratio of 8:1:1, ground and mixed to obtain an active slurry, and the active slurry was coated on a rectangular titanium mesh with a size of 1×2 cm, placed in a vacuum drying oven at 60° C. and dried for 12 h, and then pressed at a pressure of 10 MPa to obtain a working electrode; to ensure complete penetration of the electrolyte, the working electrode was immersed in the electrolyte for more than 12 h before the electrochemical test;
[0297] (2) Electrochemical testing
[0298] The prepared working electrode was subjected to constant current charge and discharge test and cycle stability test in 6 mol / L KOH electrolyte using CHI660E electrochemical workstation produced by Shanghai Chenhua Instrument Co., Ltd.
[0299] The constant current charge and discharge test records the curve of voltage change over time at a given current density, and calculates the specific capacitance and energy density of the working electrode at a current density of 0.5A / g through the constant current charge and discharge curve.
[0300] The specific capacitance of the working electrode is calculated using the following formula:
[0301]
[0302] Where C is the specific capacitance of the working electrode (F / g), I is the discharge current (A), ∆t is the discharge time (s), ∆V is the potential window (V), and m is the mass of the active slurry on the working electrode (g).
[0303] The energy density of the working electrode is calculated using the following formula:
[0304]
[0305] Where E is the energy density (Wh / kg), C is the specific capacitance of the working electrode (F / g), and ∆V is the potential window (V).
[0306] Long cycle life and stable performance are obvious advantages of supercapacitors in practical applications. The present invention adopts a blue battery testing system to charge and discharge the supercapacitor 5000 times at a constant current density of 10A / g, and calculates the capacitance retention rate (%) of the supercapacitor.
[0307] The test results of the electrochemical properties of the porous carbon materials prepared in Examples 1-5 and Comparative Examples 1-8 are shown in Table 1.
[0308] Table 1 Test results of electrochemical properties of porous carbon materials prepared in Examples 1-5 and Comparative Examples 1-8
[0309]
[0310] It can be seen from the data in Table 1 that the specific capacitance, energy density and capacitance retention rate of the porous carbon materials prepared in Examples 1-5 of the present invention are higher than those in Comparative Examples 1-8, which indicates that the highly conductive porous carbon material prepared by the preparation method provided by the present invention meets the requirements of supercapacitors for the electrochemical properties of battery materials.
[0311] It can be seen from the test data of Example 1, Comparative Example 1 and Comparative Example 2 that the specific capacitance, energy density and capacitance retention rate of the porous carbon materials prepared in Comparative Example 1 and Comparative Example 2 are lower than those in Example 1. This is because the amount of sulfonated polystyrene microspheres in Comparative Example 1 is too low and the amount of dopamine is too high, while the amount of sulfonated polystyrene microspheres in Comparative Example 2 is too high and the amount of dopamine is too low, which affects the thickness and morphology of the carbon shell skeleton obtained after carbonization of the polydopamine layer, and ultimately leads to a decrease in the electrochemical performance of the porous carbon material.
[0312] It can be seen from the test data of Example 1, Comparative Example 3 and Comparative Example 4 that the specific capacitance, energy density and capacitance retention rate of the porous carbon materials prepared in Comparative Example 3 and Comparative Example 4 are lower than those in Example 1. This is because the amount of modified carbon nanotubes added in Comparative Example 3 is too low, and the amount of modified carbon nanotubes added in Comparative Example 4 is too high, which affects the porous network morphology of the composite porous material composed of modified carbon nanotubes and Ni / Co-MOF materials, and ultimately leads to a decrease in the electrochemical performance of the porous carbon material.
[0313] It can be seen from the test data of Example 1, Comparative Example 5 and Comparative Example 6 that the specific capacitance, energy density and capacitance retention rate of the porous carbon materials prepared in Comparative Example 5 and Comparative Example 6 are lower than those in Example 1. This is because the hydrothermal reaction temperature of the carbon sphere precursor solution in Comparative Example 5 is too low, and the hydrothermal reaction temperature of the carbon sphere precursor solution in Comparative Example 6 is too high, which affects the lamellar structure of the Ni / Co-MOF material and ultimately leads to a decrease in the electrochemical performance of the porous carbon material.
[0314] It can be seen from the test data of Example 1, Comparative Example 7 and Comparative Example 8 that the specific capacitance, energy density and capacitance retention rate of the porous carbon materials prepared in Comparative Example 7 and Comparative Example 8 are lower than those in Example 1. This is because the amount of ammonium molybdate used in Comparative Example 7 is too low, and the amount of ammonium molybdate used in Comparative Example 8 is too high, which affects the morphology of molybdenum disulfide and fails to form clustered microspheres with a nanosheet structure, ultimately resulting in a decrease in the electrochemical performance of the porous carbon material.
[0315] The applicant declares that the above is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention shall fall within the protection scope and disclosure scope of the present invention.
Claims
1. A method for preparing a highly conductive porous carbon material, characterized in that: The preparation method comprises: Firstly, polystyrene microspheres are sulfonated and coated with polydopamine to obtain coated modified polystyrene microspheres; Subsequently, the carbon nanotubes are modified to obtain modified carbon nanotubes; cobalt and nickel are used as metal centers, 2-methylimidazole is used as an organic ligand, and the modified carbon nanotubes are used as conductive fillers. A composite porous material composed of the modified carbon nanotubes and the Ni / Co-MOF material is synthesized in situ on the surface of the coated modified polystyrene microspheres by a hydrothermal synthesis method, and finally a hollow carbon sphere precursor composed of the coated modified polystyrene microspheres and the composite porous material loaded on the surface of the coated modified polystyrene microspheres is obtained; Finally, ammonium molybdate and thiourea are used as raw materials to generate molybdenum disulfide nanosheets by in-situ reaction on the surface of the hollow carbon sphere precursor to obtain the highly conductive porous carbon material; The preparation method specifically comprises the following steps: (I) adding polystyrene microsphere seeds, dibutyl phthalate and toluene to a sodium dodecyl sulfate solution, while mechanically stirring and heating in a water bath to obtain a microsphere emulsion; adding styrene monomer, divinylbenzene monomer and 2,2-azobisisobutyronitrile to the sodium dodecyl sulfate solution, mixing uniformly to obtain a microsphere precursor solution; adding the microsphere precursor solution to the microsphere emulsion, mixing uniformly to obtain a reaction precursor solution, adding polyvinyl alcohol solution to the reaction precursor solution, mixing uniformly to obtain a reaction solution, heating and stirring the reaction solution in an anaerobic environment to react, and sequentially washing the reaction product with deionized water, Soxhlet extraction, anhydrous ethanol washing, centrifugal separation and vacuum drying to obtain polystyrene microspheres; (II) dispersing the polystyrene microspheres obtained in step (I) in an ethanol aqueous solution, ultrasonically dispersing to obtain a microsphere dispersion liquid, adding concentrated sulfuric acid to the microsphere dispersion liquid, ultrasonically dispersing to obtain a sulfonated microsphere solution, heating and stirring the sulfonated microsphere solution to react, filtering, washing and drying after the reaction to obtain sulfonated polystyrene microspheres; dissolving dopamine in a Tris-HCl buffer, mixing uniformly to obtain a dopamine solution; dispersing the sulfonated polystyrene microspheres in the dopamine solution, stirring at room temperature to allow dopamine to polymerize in situ on the surface of the sulfonated polystyrene microspheres to form a polydopamine layer, and then filtering, washing and drying to obtain coated modified polystyrene microspheres; (III) dispersing carbon nanotubes in a mixed acid solution composed of concentrated sulfuric acid and concentrated nitric acid, obtaining a first dispersion after ultrasonic dispersion, heating and stirring the first dispersion, and then filtering, washing and drying to obtain first carbon nanotubes; dispersing the first carbon nanotubes in an acidic hydrogen peroxide solution to obtain a second dispersion, applying high temperature and high pressure to the second dispersion under a protective atmosphere to react, and obtaining second carbon nanotubes after the reaction; uniformly mixing the second carbon nanotubes, polyethylene glycol 2000, polyvinyl pyrrolidone and deionized water to obtain a third dispersion, refluxing the third dispersion under a nitrogen atmosphere, and filtering, washing and drying to obtain modified carbon nanotubes after the reaction; (IV) mixing the modified carbon nanotubes, polyvinyl pyrrolidone and methanol obtained in step (III), and obtaining a carbon nanotube suspension by ultrasonic dispersion, adding cobalt nitrate hexahydrate and nickel nitrate hexahydrate to the carbon nanotube suspension, and obtaining a metal salt solution by ultrasonic dispersion, and adding the coated modified polystyrene microspheres obtained in step (II) to the metal salt solution, and mixing them uniformly to obtain a precursor solution; dissolving 2-methylimidazole in methanol to obtain an organic ligand solution; and uniformly mixing the precursor solution and the organic ligand solution to obtain a carbon sphere precursor solution, subjecting the carbon sphere precursor solution to a hydrothermal reaction, and washing, centrifuging and drying the reaction product obtained by the reaction to obtain a hollow carbon sphere precursor; (V) spreading the hollow carbon sphere precursor obtained in step (IV) in a first porcelain boat, spreading sodium hypophosphite in a second porcelain boat, placing the first porcelain boat and the second porcelain boat in a tubular furnace with a distance therebetween, introducing a mixed gas of hydrogen and nitrogen into the tubular furnace, performing a phosphating reaction on the hollow carbon sphere precursor, washing and drying the reaction product obtained by the reaction, and obtaining a phosphated hollow carbon sphere precursor; heating the phosphated hollow carbon sphere precursor to a first temperature at a first heating rate and keeping the temperature, then heating the phosphated hollow carbon sphere precursor to a second temperature at a second heating rate and keeping the temperature, and finally cooling the precursor to room temperature with the furnace to complete the carbonization treatment and obtain a hollow carbon sphere composite material; (VI) dispersing the hollow carbon sphere composite material obtained in step (V) in anhydrous ethanol to obtain a carbon sphere dispersion; dissolving ammonium molybdate and thiourea in anhydrous ethanol to obtain a MoS2 precursor solution; mixing the carbon sphere dispersion with the MoS2 precursor solution, and obtaining a reaction mixture after ultrasonic dispersion; heating the reaction mixture to a third temperature at a third heating rate and keeping the temperature, and then heating the reaction mixture to a fourth temperature at a fourth heating rate and keeping the temperature, and cooling the reaction mixture to room temperature in the furnace after the insulation is completed, so that ammonium molybdate and thiourea react to generate molybdenum disulfide nanosheets and load them on the surface of the hollow carbon sphere composite material to obtain the highly conductive porous carbon material.
2. The method for preparing a highly conductive porous carbon material according to claim 1, characterized in that: In step (I), the particle size of the polystyrene microsphere seeds is 2-3 μm; The mass fraction of the sodium dodecyl sulfate solution is 0.2-0.3wt%; The ratio of the polystyrene microsphere seeds, the dibutyl phthalate, the toluene and the sodium dodecyl sulfate solution is 1 g: (5-10) mL: (15-20) mL: (100-150) mL; The rotation speed of the mechanical stirring is 400-500 rpm; The water bath heating temperature is 30-40°C; The water bath heating time is 20 to 30 hours; The ratio of the total volume of the styrene monomer and the divinylbenzene monomer to the volume of the sodium dodecyl sulfate solution is (0.02-0.03):1; The volume ratio of the styrene monomer to the divinylbenzene monomer is 1:(0.4-0.5); The mass ratio of the 2,2-azobisisobutyronitrile to the styrene monomer is (0.02-0.03):1; The mass ratio of the styrene monomer in the microsphere precursor solution to the polystyrene microsphere seeds in the microsphere emulsion is (100-120):1; The mass ratio of the styrene monomer in the reaction precursor solution to the polyvinyl alcohol in the polyvinyl alcohol solution is (0.1-0.2):1; The mass fraction of the polyvinyl alcohol solution is 10-12wt%; The stirring rate of the reaction solution is 100-150 rpm; The heating temperature of the reaction solution is 65-75°C; The heating time of the reaction solution is 20 to 30 hours; The solvent used in the Soxhlet extraction is obtained by mixing methanol and acetic acid in a volume ratio of (8-9):(1-2); The Soxhlet extraction time is 5 to 10 hours; The temperature of the Soxhlet extraction is 75-85°C.
3. The method for preparing a highly conductive porous carbon material according to claim 1, characterized in that: In step (II), the mass ratio of the polystyrene microspheres to the ethanol aqueous solution is 1:(20-30); The volume ratio of ethanol to deionized water in the ethanol aqueous solution is 1:(1.5-2); The ultrasonic power of the ultrasonic dispersion of the polystyrene microspheres dispersed in the ethanol aqueous solution is 300-400W; The ultrasonic dispersion time of the polystyrene microspheres after being dispersed in the ethanol aqueous solution is 1 to 2 hours; The mass ratio of the polystyrene microspheres in the microsphere dispersion to the concentrated sulfuric acid is 1:(20-25); The mass fraction of the concentrated sulfuric acid is 80-90wt%; The ultrasonic power of ultrasonic dispersion after adding concentrated sulfuric acid to the microsphere dispersion is 400-500W; The ultrasonic dispersion time after adding concentrated sulfuric acid to the microsphere dispersion is 10 to 20 minutes; The heating temperature of the sulfonated microsphere solution is 30-40°C; The heating time of the sulfonated microsphere solution is 2 to 3 hours; The concentration of dopamine in the dopamine solution is 5-8 g / L; The pH value of the dopamine solution is 8-9; The mass ratio of the sulfonated polystyrene microspheres to the dopamine in the dopamine solution is (1.5-2.5):1; The sulfonated polystyrene microspheres are dispersed in the dopamine solution and stirred for 20 to 30 hours.
4. The method for preparing a highly conductive porous carbon material according to claim 1, characterized in that: In step (III), the molar concentration of the concentrated sulfuric acid is 17-18 mol / L; The molar concentration of the concentrated nitric acid is 15-16 mol / L; The volume ratio of the concentrated sulfuric acid to the concentrated nitric acid is 1:(3-4); The ratio of the carbon nanotubes to the mixed acid solution is 1 g: (100-200) mL; The heating temperature of the first dispersion is 50-60°C; The stirring time of the first dispersion is 1 to 2 hours; The acidic hydrogen peroxide solution is obtained by mixing glacial acetic acid, hydrogen peroxide solution and concentrated sulfuric acid in a volume ratio of (8-9):(4-5):1, wherein the mass fraction of the hydrogen peroxide solution is 30-40wt%, and the mass fraction of the concentrated sulfuric acid is 95-98wt%; The ratio of the first carbon nanotube to the acidic hydrogen peroxide solution is 1 g: (200-300) mL; The reaction temperature of the second dispersion is 140-150°C; The reaction pressure of the second dispersion is 0.8-1.2 MPa; The reaction time of the second dispersion is 30 to 40 minutes; The mass ratio of the polyethylene glycol 2000 to the polyvinyl pyrrolidone is (2-3):1; The ratio of the total mass of the polyethylene glycol 2000 and the polyvinyl pyrrolidone to the mass of the second carbon nanotube is (1-2):1; The mass fraction of the second carbon nanotubes in the third dispersion is 1-5wt%; Before the reflux reaction begins, adding an acid solution dropwise to the third dispersion to adjust the pH value of the third dispersion to 2-4; The temperature of the reflux reaction is 80-90°C; The reflux reaction time is 3 to 5 hours.
5. The method for preparing a highly conductive porous carbon material according to claim 1, characterized in that: In step (IV), the mass fraction of the modified carbon nanotubes in the carbon nanotube suspension is 20-30 wt %; The ratio of the modified carbon nanotubes, polyvinyl pyrrolidone and methanol is (40-50) g: (80-90) g: (90-100) L; The ultrasonic power of the ultrasonic dispersion after the modified carbon nanotubes, polyvinyl pyrrolidone and methanol are mixed is 150-250W; The ultrasonic dispersion time of the modified carbon nanotubes, polyvinyl pyrrolidone and methanol after mixing is 50 to 60 minutes; The mass ratio of the modified carbon nanotubes, the cobalt nitrate hexahydrate and the nickel nitrate hexahydrate in the carbon nanotube suspension is 1:(20-30):(40-50); The ultrasonic power of ultrasonic dispersion after adding the cobalt nitrate hexahydrate and the nickel nitrate hexahydrate to the carbon nanotube suspension is 300-400W; The ultrasonic dispersion time after adding the cobalt nitrate hexahydrate and the nickel nitrate hexahydrate into the carbon nanotube suspension is 20 to 30 minutes; The ratio of the total mass of cobalt nitrate hexahydrate and nickel nitrate hexahydrate in the metal salt solution to the mass of the coated modified polystyrene microspheres is (2-3):1; The mass ratio of the 2-methylimidazole to methanol is 1:(20-30); The mass ratio of the total mass of cobalt nitrate hexahydrate and nickel nitrate hexahydrate in the precursor solution to the mass ratio of 2-methylimidazole in the organic ligand solution is 1:(1.5-2); The temperature of the hydrothermal reaction of the carbon sphere precursor solution is 160-170°C; The hydrothermal reaction time of the carbon sphere precursor solution is 12 to 24 hours; The rotation speed of the centrifugal separation is 5000-6000 r / min; The centrifugal separation time is 3 to 5 minutes.
6. The method for preparing a highly conductive porous carbon material according to claim 1, characterized in that: In step (V), the mass ratio of the hollow carbon sphere precursor to the sodium hypophosphite is 1:(20-30); The distance between the first porcelain boat and the second porcelain boat is 10-20 cm; The volume ratio of hydrogen to nitrogen in the mixed gas is (1-2):(8-9); The flow rate of the mixed gas is 90-100 mL / min; The pressure in the tube furnace is 2-3 MPa; The heating rate of the phosphating reaction is 4-5°C / min; The heating temperature of the phosphating reaction is 300-400°C; The holding time of the phosphating reaction is 70 to 80 minutes; The first heating rate is 3-4°C / min; The first temperature is 400-500° C.; Keep warm at the first temperature for 1 to 2 hours; The second heating rate is 5-6°C / min; The second temperature is 700-800°C; Keep at the second temperature for 2 to 3 hours.
7. The method for preparing a highly conductive porous carbon material according to claim 1, characterized in that: In step (VI), the ratio of the hollow carbon sphere composite material to anhydrous ethanol is 1 g: (100-200) mL; The ratio of the ammonium molybdate, the thiourea and the anhydrous ethanol is 1 g: (2-3) g: (80-90) mL; The mass ratio of the hollow carbon sphere composite material in the carbon sphere dispersion to the ammonium molybdate in the MoS2 precursor solution is 1:(1.5-2.5); The ultrasonic power of the ultrasonic dispersion after the carbon sphere dispersion and the MoS2 precursor solution are mixed is 200-300W; The ultrasonic dispersion time of the carbon sphere dispersion and the MoS2 precursor solution after mixing is 30 to 40 minutes; The third heating rate is 2-3°C / min; The third temperature is 100-120° C. Keep warm at the third temperature for 4 to 5 hours; The fourth heating rate is 1-2°C / min; The fourth temperature is 180-200° C. Keep warm at the fourth temperature for 6 to 8 hours.
8. A highly conductive porous carbon material prepared by the method for preparing a highly conductive porous carbon material according to any one of claims 1 to 7.
9. Use of the highly conductive porous carbon material according to claim 8 in an energy storage device, characterized in that: The energy storage device includes a supercapacitor.
